Method for producing white uv-absorbing surface-reacted calcium carbonate doped with titanium species, white uv-absorbing surface-reacted calcium carbonate and use thereof

A method for producing white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species addresses health and environmental concerns by integrating titanium into calcium carbonate particles, achieving high surface area and UV-absorbing properties for diverse applications.

CN119213084APending Publication Date: 2024-12-27OMYA INT AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041339.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-05-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing methods for producing calcium carbonate-based fillers and pigments face challenges due to the potential carcinogenicity of submicron and nanometer-sized titanium dioxide particles, leading to health risks and environmental concerns, while also requiring complex and costly processes.

Method used

A method involving the treatment of calcium carbonate with calcium phosphate in an aqueous medium at a pH of at least 4.2, combined with titanium-containing substances, to produce white, UV-absorbing, surface-reacted calcium carbonate particles, ensuring the titanium species are integrated and not separable by washing, using lower-quality raw materials and standard equipment.

Benefits of technology

The method produces particles with high surface area and UV-absorbing properties, avoiding health risks and environmental persistence, suitable for various applications without the need for titanium dioxide in powder form, and is cost-effective and easy to handle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140883610000591
    Figure BDA0005140883610000591
Patent Text Reader

Abstract

The invention relates to a method for producing white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species, comprising the following steps: providing a material comprising calcium carbonate, a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate, and at least one species comprising titanium, treating the calcium carbonate-containing material with the calcium phosphate in an aqueous medium to form an aqueous suspension and grinding the aqueous suspension at a pH of at least 4.2 to form an aqueous suspension of surface-reacted calcium carbonate, wherein the calcium carbonate-containing material and the calcium phosphate combination have a molar ratio of calcium ions to phosphate ions (Ca2 +: PO4 < 3->) in the range of 1.75: 1 to 100: 1, and wherein the at least one titanium-containing substance is added before and / or during and / or after the treatment step and / or before and / or during the grinding step.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for producing a white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium species, comprising the steps of providing a calcium carbonate-containing material, a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate, and at least one titanium-containing material and treating the calcium carbonate-containing material with the calcium phosphate in an aqueous medium to form an aqueous suspension and grinding the aqueous suspension at a pH of at least 4.2 to form an aqueous suspension of a white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium species, wherein the calcium carbonate-containing material and the calcium phosphate combination have a calcium ion to phosphate ion molar ratio (Ca 2+ / - 2H 2O ) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ), and wherein at least one substance comprising titanium is added before and / or during and / or after the treatment step and / or before and / or during the grinding step. Furthermore, the present invention relates to a white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium substance obtained by this method, the use of said white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium substance and an article comprising said white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium substance. Background Art

[0002] Mineral fillers, and especially those containing calcium carbonate, are often used as particulate fillers added to resins or adhesives, paints or papers and can improve specific properties such as opacity, brightness, stability, viscosity, strength or stiffness and can make the product cheaper, or a mixture of both.

[0003] EP2997833 relates to the use of surface-reacted calcium carbonate as an anti-caking agent, wherein the surface-reacted calcium carbonate is the reaction product of natural ground or precipitated calcium carbonate with carbon dioxide and at least one acid in an aqueous medium, wherein the at least one acid is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, citric acid, oxalic acid, acetic acid, formic acid and mixtures thereof, wherein the carbon dioxide is generated in situ by acid treatment and / or supplied from an external source, and wherein the surface-reacted calcium carbonate particles have a volume median particle size d of 0.1-50 μm. 50 .

[0004] EP2926797 relates to an oral care composition for tooth remineralization and / or whitening comprising surface-reacted calcium carbonate, wherein the surface-reacted calcium carbonate is the reaction product of natural or synthetic calcium carbonate with carbon dioxide and at least one acid.

[0005] EP20186219.0 relates to a curable fluoropolymer composition comprising a crosslinkable fluoropolymer and surface-reacted calcium carbonate as filler.

[0006] EP3693339 relates to a process for producing an aqueous suspension of surface-reacted calcium salt particles by mixing a calcium salt other than monocalcium phosphate and dicalcium phosphate, a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate, with water and grinding the obtained aqueous suspension at a pH of at least 4.2 to form an aqueous suspension of surface-reacted calcium salt particles.

[0007] In addition, other pigments and particles are often added, which add further advantageous features to the filler composition. Pigments or particles are generally known as materials that change the color of reflected or transmitted light due to wavelength selective absorption. This physical process is different from fluorescence, phosphorescence and other forms of luminescence (material emitting light therein). Pigments are used for coloring, such as paints, inks, plastics, fabrics, cosmetics, food and other materials. Most of the pigments used are dry colorants, usually ground into fine powder.

[0008] White pigments occupy a special place in the pigment world due to their industrial relevance. For example, the European paper industry uses more than 10 million tons of white pigments every year. White pigments are also used in paints and coatings. Especially in the manufacture of dispersion paints, white pigments are the base color of the coloring system.

[0009] A known white pigment is titanium dioxide, also known as titanium white, pigment white 6 (PW6), CI77891 or E number E171. Typically, it is derived from ilmenite, rutile, and anatase or mixtures thereof. It has a wide range of applications, especially as a white pigment in paper and plastic materials and paints. In addition, due to its white color, it is also used as food coloring or cosmetic applications. In addition, titanium dioxide is able to absorb ultraviolet rays and is therefore often used in sunscreens and sunscreen applications.

[0010] EP0634462 relates to a coating composition containing very finely divided TiO2, comprising 0.5-30.0% by volume of color pigments and / or carbon black, 55.0-98.5% by volume of binder solids and 0.3-15.0% by volume of very finely divided TiO2 (particle size 5-40 nm), and having a high total reflectivity (brightness) and a strong depth of color.

[0011] EP2188125 relates to a self-cleaning, defouling paint comprising from about 5% to about 40% by volume of photocatalytic titanium dioxide in substantially pure anatase form, characterized by an average crystallite size between about 5 nm and about 30 nm and having photocatalytic activity in the presence of visible light; one or more additional pigments, and a styrene acrylic copolymer binder.

[0012] US7476704 relates to a polymer composition comprising a polymer resin, a flash calcined kaolin clay filler and a titanium dioxide filler. The titanium dioxide has an average aggregate size in the range of about 0.2-0.35 μm.

[0013] AU630406 relates to titanium dioxide particles having an average primary particle size of less than 100 nm, each of which is substantially coated with a phospholipid. The phospholipid-coated titanium dioxide particles can be incorporated into oil-in-water and water-in-oil emulsions to provide novel sunscreen compositions having excellent UV shielding efficiency, long-term stability and water resistance properties.

[0014] EP 3360601 relates to a cosmetic composition with UV-A and / or UV-B protection, comprising at least one inorganic UV filter and having a volume median particle size d 50 Surface-reacted calcium carbonate with a diameter of 0.1-90 μm, wherein the surface-reacted calcium carbonate is natural ground calcium carbonate or precipitated calcium carbonate with carbon dioxide and one or more H3O + The reaction product of the ion donor, wherein the carbon dioxide is composed of H3O + The ion donor treatment is formed in situ and / or supplied from an external source.However, in this patent application only a mixture of inorganic UV filters and surface-reacted calcium carbonate is provided, but the structure of the surface-reacted calcium carbonate is not modified.

[0015] EP3517176 relates to a particle having a volume median particle size d 50 Use of surface-reacted calcium carbonate with a diameter of 0.1 to 90 μm as a skin appearance regulator in cosmetic and / or skin care compositions, wherein the surface-reacted calcium carbonate is natural ground calcium carbonate or precipitated calcium carbonate with carbon dioxide and one or more H3O + The reaction product of the ion donor, wherein the carbon dioxide is composed of H3O + The ion donor is formed in situ and / or supplied from an external source. EP3517178 relates to the use of surface-reacted calcium carbonate as an agent for modifying the biomechanical properties of the skin in a cosmetic and / or skin care composition, wherein the surface-reacted calcium carbonate has a volume median particle size d 50 0.1-90 μm, and wherein the surface-reacted calcium carbonate is natural ground calcium carbonate or precipitated calcium carbonate with carbon dioxide and one or more H3O + The reaction product of the ion donor, wherein the carbon dioxide is composed of H3O +The ion donor treatment is formed in situ and / or supplied by an external source. The cosmetic and / or skin care composition may contain further additives, such as inorganic UV filters, for example titanium dioxide. However, these documents also only relate to mixtures of inorganic UV filters and surface-reacted calcium carbonate, but do not modify the structure of the surface-reacted calcium carbonate.

[0016] However, in some applications, titanium dioxide is used in the form of a powder containing submicron or nanometer sized titanium dioxide particles. This is disadvantageous because submicron and / or nanometer sized TiO2 powders are problematic due to the potential carcinogenicity of such small titanium dioxide particles. Due to this potential carcinogenicity, the European Union is attempting to ban such particles at least in food and cosmetic applications.

[0017] Another disadvantage is that when the two compounds (surface-reacted calcium carbonate and titanium-containing material, such as titanium dioxide) are mixed in the form of a dry product, this can lead to the generation of aerosols which can cause health problems, especially when inhaled.

[0018] In view of the above, there is a continuing need for a process for producing particles or fillers comprising surface-reacted calcium carbonate and titanium species and having excellent properties in terms of their color, their UV absorbance and in terms of their mechanical and particle properties.

[0019] It is therefore an object of the present invention to provide a method for preparing an improved filler or improved particle comprising surface-reacted calcium carbonate and useful in polymer applications, paper coating applications, papermaking, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications. The filler or particle should have a white appearance so that they are particularly useful in paints and paper without adding unwanted color to such applications.

[0020] Furthermore, it is desirable to provide a method for preparing fillers or particles which have UV absorbing properties and can be used in medicine, such as tablet coatings or implants, or in cosmetics, especially in sunscreen and sun protection applications. The fillers or particles and the method should be non-toxic to humans, have no harmful effects on the environment, and can be used in cosmetic applications.

[0021] In particular, the fillers or particles obtained by this process should be free of titanium dioxide in the submicron and / or nanometer size range in order to avoid health problems, in particular the carcinogenicity of such products. Furthermore, the fillers and particles obtained by this process should have a defined crystal structure. In addition, it is desirable that by this process the titanium species cannot be separated from the surface-reacted calcium carbonate by washing alone or in a liquid composition.

[0022] Another object of the invention is that the method for producing fillers or particles should be easy and fast to produce, affordable and especially easy to handle.In addition, it is also an object of the invention to provide a material which is at least partly derived from natural sources and is not persistent in the environment.

[0023] In addition, the object of the present invention is to provide an economical method, which can utilize raw materials with lower quality such as by-products or waste materials of other methods. It is also desirable to provide a method that can utilize raw materials. In addition, the method for producing white UV-absorbing surface-reacted calcium carbonate particles should be able to be carried out as a continuous process and should be able to operate at low starting temperatures. It is desirable to provide a method that can be carried out using standard equipment. Summary of the invention

[0024] The foregoing and other objects are solved by the subject matter as defined in the independent claims.

[0025] According to one aspect of the present invention, there is provided a method for producing white UV absorbing titanium doped surface reacted calcium carbonate comprising the following steps:

[0026] a) providing a material comprising calcium carbonate,

[0027] b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate,

[0028] c) providing at least one substance comprising titanium, and

[0029] d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and

[0030] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0031] wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0032] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0033] According to another aspect of the present invention, there is provided a white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species obtainable by the process according to the present invention.

[0034] The inventor has surprisingly found that the surface-reacted calcium carbonate particles doped with titanium substances can be prepared by the inventive method. The method for producing these particles is an easy and fast method, and the product obtained is affordable and especially easy to handle. The method can be carried out in standard equipment without causing a significant burden on humans and the environment. In addition, the inventor has surprisingly found that a material can be provided by the method of the present invention, which is at least partially derived from natural sources and is not persistent in the environment. The inventor has also surprisingly found that raw materials with lower quality, such as by-products or waste materials of other methods, and especially raw materials can be used in the inventive method.

[0035] Such a process and product are advantageous because the final consumer does not have to handle particles comprising titanium dioxide in powder form, said powder comprising submicron or nanometer sized titanium dioxide particles. Instead, the particles obtained comprise the advantageous properties of surface-reacted calcium carbonate and have in particular a high surface area and are furthermore white and UV absorbing. Furthermore, the particles obtained by the inventive process are advantageous because the titanium species cannot be separated from the surface-reacted calcium carbonate by washing alone or in a liquid composition.

[0036] The obtained white UV absorbing surface reacted calcium carbonate doped with titanium species can be used in a variety of applications such as paints, paper, coatings or sunscreens. Such products do not have to be labeled as titanium dioxide particles in the submicron and / or nanometer size range in the ingredient list and should therefore have a higher acceptance by the end consumer. The fillers or particles should have a white appearance so that they are particularly useful in paints and paper without adding unwanted color to such applications.

[0037] According to another aspect of the present invention, the white UV absorbing surface-reacted calcium carbonate doped with titanium species obtainable by the process of the present invention is used in polymer applications, paper coating applications, papermaking, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications.

[0038] According to another aspect of the invention, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium substances obtainable by the process of the invention is used for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

[0039] According to another aspect of the present invention, there is provided an article comprising a white, UV-absorbing, surface-reacted calcium carbonate doped with a titanium species obtainable by the process of the present invention, wherein the article is selected from the group consisting of paper products, engineered wood products, gypsum board products, polymer products, hygiene products, medical products, health products, filtration products, woven materials, non-woven materials, geotextile products, agricultural products, horticultural products, clothing, footwear products, luggage products, household products, industrial products, packaging products, building products and construction products.

[0040] Advantageous embodiments of the above aspects are defined in the respective dependent claims.

[0041] According to one embodiment of the present invention, the material comprising calcium carbonate is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably natural ground calcium carbonate is selected from marble, chalk, limestone and mixtures thereof, and / or the precipitated calcium carbonate is selected from precipitated calcium carbonate having aragonite, vaterite or calcite crystal form and mixtures thereof.

[0042] According to another embodiment of the present invention, the calcium carbonate containing material is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-20 μm. 50 (weight), and / or a weight top cut particle size d of 0.15-1500 μm, preferably 1-600 μm, more preferably 1.5-300 μm and most preferably 2-80 μm. 98 (weight).

[0043] According to another embodiment of the present invention, the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.9:1 to 75:1, preferably 2:1 to 50:1, more preferably 2.2:1 to 25:1 and most preferably 2.5:1 to 10:1. 2+ :PO4 3- ).

[0044] According to another embodiment of the present invention, the calcium phosphate of step b) is dicalcium phosphate dihydrate and is provided in an amount of 1.7-230 wt. %, preferably 2.3-191 wt. %, more preferably 3.5-172 wt. % and most preferably 19-115 wt. %, based on the total weight of the calcium carbonate-containing material of step a), or

[0045] wherein the calcium phosphate of step b) is anhydrous dicalcium phosphate and is provided in an amount of 1.4-181 wt. %, preferably 1.8-151 wt. %, more preferably 2.8-136 wt. % and most preferably 15-91 wt. %, based on the total weight of the calcium carbonate-containing material of step a), or

[0046] wherein the calcium phosphate of step b) is anhydrous monocalcium phosphate and is provided in an amount of 1.2-94 wt. %, preferably 1.6-84 wt. %, more preferably 2.4-78 wt. % and most preferably 12-59 wt. %, based on the total weight of the calcium carbonate-containing material of step a), or

[0047] Wherein the calcium phosphate of step b) is monocalcium phosphate monohydrate and is provided in an amount of 1.3-100 wt.-%, preferably 1.7-90 wt.-%, more preferably 2.5-84 wt.-% and most preferably 13-63 wt.-%, based on the total weight of the calcium carbonate-containing material of step a).

[0048] According to another embodiment of the present invention, at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium dioxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

[0049] According to another embodiment of the present invention, the at least one substance comprising titanium is provided in an amount of 0.1-20 wt. % titanium element, preferably 0.5-15 wt. %, more preferably 1.0-10 wt. % and most preferably 2.5-7.5 wt. %, based on the total dry weight of the material comprising calcium carbonate.

[0050] According to another embodiment of the present invention, the aqueous suspension formed in step d) has a solids content of 1-95 wt.-%, preferably 3-75 wt.-%, more preferably 5-50 wt.-%, even more preferably 7-30 wt.-%, even more preferably 9-25 wt.-% and most preferably 10-20 wt.-%, based on the total weight of the aqueous suspension, and / or wherein in step d) the material comprising calcium carbonate is treated with a solution comprising calcium carbonate from step b) and at least one substance comprising titanium from step c).

[0051] According to another embodiment of the present invention, step e) is carried out at a pH value of 4.5-14, preferably at a pH value of 4.7-13.5, more preferably at a pH value of 5-13, even more preferably at a pH value of 5.5-12.5, even more preferably at a pH value of 6-12 and most preferably at a pH value of 6.0-8.0.

[0052] According to another embodiment of the present invention, step d) and / or in step e) is carried out at a temperature of 10-100°C, preferably 15-80°C, more preferably 20-50°C and most preferably 20±2°C.

[0053] According to another embodiment of the present invention, dicalcium phosphate is produced by the following steps:

[0054] i) providing a source of calcium ions other than dicalcium phosphate, preferably providing a material comprising calcium carbonate, more preferably providing natural ground calcium carbonate,

[0055] ii) providing a phosphate ion source selected from phosphoric acid, its salts and mixtures thereof, preferably phosphoric acid, and

[0056] iii) contacting the calcium ion source of step i) and the phosphate ion source of step ii) in the presence of water to form dicalcium phosphate,

[0057] wherein the source of calcium ions of step i) and the source of phosphate ions of step ii) are provided in combination in a molar ratio of calcium ions to phosphate ions of 1:2 to 5:1, preferably 2:3 to 2:1, more preferably 3:4 to 3:2, even more preferably 5:6 to 4:3, still more preferably 10:11 to 11:10 and most preferably about 1:1.

[0058] According to another embodiment of the present invention, steps b) and d) are replaced by the following steps B) and D):

[0059] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof, and

[0060] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate,

[0061] wherein the molar ratio of calcium ions to phosphate ions (Ca) is in the range of 1.75:1 to 100:1. 2+ :PO4 3- ) provide the calcium carbonate-containing material of step a) and the phosphate ion source of step b).

[0062] According to another embodiment of the present invention, the phosphate ion source is phosphoric acid, a non-hydrogen-containing salt of phosphoric acid, a monohydrogen salt of phosphate, preferably Na2HPO4, or a dihydrogen salt of phosphate, or a mixture thereof. Preferably, the phosphate ion source is phosphoric acid, a dihydrogen salt of phosphate, or a mixture thereof. Preferably, the phosphate ion source is selected from phosphoric acid, NaH2PO4, KH2PO4, LiH2PO4, NH4H2PO4, Ca(H2PO4)2, Mg(H2PO4)2, and a mixture thereof.

[0063] According to another embodiment of the present invention, the method further comprises a step f) of separating the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e), and preferably step f) is performed by solvent evaporation and / or filter pressing, and / or

[0064] Wherein the process further comprises the step g): drying the surface-reacted calcium carbonate doped with titanium species at a temperature in the range of 60-600° C., preferably 80-450° C., most preferably 95-400° C. after step e) or after step f) (if present), preferably until the moisture content of the surface-reacted calcium carbonate doped with titanium species is less than 1 wt.-%, based on the total weight of the dried surface-reacted calcium carbonate.

[0065] It should be understood that for the purposes of the present invention, the following terms have the following meanings:

[0066] "White" pigments or "white" particles or "white" filler materials within the meaning of the present invention are solid inorganic coloring materials with a defined chemical composition and characteristic crystalline structure. Such materials are insoluble in water and therefore result in suspensions when in contact with water. They have a white appearance when irradiated with daylight.

[0067] "UV-absorbing" pigments or particles in the meaning of the present invention absorb at least some of the ultraviolet B (UV-B) radiation in the range of 280-320 nm and the ultraviolet A (UV-A) radiation in the range of >320 to 400 nm.

[0068] As used herein, the term "acid" refers to an acid within the meaning defined by Bronsted and Lowry (e.g., H2SO4, HSO4 – ), where the term "free acid" refers only to those acids in fully protonated form (e.g., H2SO4).

[0069] The term "surface-reacted" in the meaning of the present application shall be used to indicate that a material has been subjected to a process comprising partial dissolution of said material in an aqueous environment, followed by a crystallization process on and around the surface of said material, which may occur in the absence or presence of further crystallization additives. "Surface-reacted calcium carbonate" in the meaning of the present invention is the reaction product of a material comprising calcium carbonate and a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate during grinding in an aqueous medium at a pH of at least 4.2, wherein the material comprising calcium carbonate and the calcium phosphate combination have a calcium ion to phosphate ion molar ratio (Ca 2+ ) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ).

[0070] A "calcium carbonate-containing material" in the meaning of the present invention is a mineral material or synthetic material having a calcium carbonate content of at least 80% by weight, preferably 85% by weight, more preferably 90% by weight and most preferably 95% by weight, based on the total weight of the calcium carbonate-containing material.

[0071] "Natural ground calcium carbonate" (GCC also referred to as GNCC) in the meaning of the present invention is calcium carbonate obtained from natural sources such as limestone, marble, or chalk and processed by wet and / or dry treatments such as grinding, screening and / or classification, for example by cyclones or classifiers.

[0072] "Precipitated calcium carbonate" (PCC) in the meaning of the present invention is a synthetic material, obtained by precipitation after reaction of carbon dioxide and lime in an aqueous, semi-dry or humid environment or by precipitation of calcium and carbonate ion sources in water. PCC can be vaterite, calcite or aragonite crystalline form. PCC is described, for example, in EP2447213 A1, EP2524898 A1, EP2371766 A1, EP1712597A1, EP1712523 A1 or WO2013142473 A1.

[0073] A "substance comprising titanium" within the meaning of the present invention is a substance comprising titanium in ionic form or in covalently bonded form having an oxidation number other than zero.

[0074] Surface-reacted calcium carbonate "doped" with titanium species refers to surface-reacted calcium carbonate in which titanium species have been introduced into the structure of the calcium carbonate. Titanium species refers to titanium having an oxidation number other than zero.

[0075] A "salt" in the meaning of the present invention is a chemical compound composed of a combination of a cation and an anion (see IUPAC, Compendium of Chemical Terminology, 2nd edition ("Golden Book"), 1997, "Salts").

[0076] The "particle size" of a particulate material other than surface-reacted calcium carbonate (e.g., GCC or PCC) is defined herein by its particle size d x (weight) distribution description. Among them, the value d x (by weight) represents the diameter such that x weight % of the particles have a diameter smaller than d x (weight). This means that for example d 20 The (weight) value is the particle size below which 20% by weight of all particles are smaller. 50 The (weight) value is therefore the weight median particle size, i.e. the particle size below which 50% by weight of all particles are smaller and d 98 The (weight) value (called weight-based top cut) is the particle size below which 98% by weight of all particles are smaller. The weight-based median particle size d is measured by the sedimentation method. 50 (weight) and top cut d 98(weight), the sedimentation method is the analysis of sedimentation behavior in a gravitational field. The measurement was performed using a Sedigraph from Micromeritics Instrument Corporation, USA TM The method and the apparatus are known to the skilled person and are commonly used for determining the particle size distribution. The measurement is carried out in a 0.1 wt. % Na4P2O7 aqueous solution. A high-speed stirrer and sonication are used to disperse the sample.

[0077] The "particle size" of the surface-reacted calcium carbonate is described herein as the particle size distribution based on volume. x (volume). Where, the value d x (volume) represents the diameter such that x volume % of the particles have a diameter smaller than d x The diameter of a volume. This means that, for example, d 20 The (volume) value is the particle size below which 20% by volume of all particles are smaller. 50 The (volume) value is therefore the volume median particle size, i.e. the particle size below which 50% by volume of all particles are smaller and d 98 The (volume) value (called the volume-based top cut) is the particle size below which 98% by volume of all particles are smaller. The volume median particle size d is estimated using a Malvern Mastersizer 3000 laser diffraction system. 50 The d was measured using a Malvern Mastersizer 3000 laser diffraction system. 50 or 98 The value indicates the diameter value such that 50% or 98% of the particles by volume, respectively, have a diameter smaller than this value. The raw data obtained by the measurement were analyzed using Mie theory, with the particle refractive index being 1.57 and the absorptivity being 0.005.

[0078] For the purposes of the present invention, "porosity" or "pore volume" refers to the intrusion specific pore volume within a particle. In the context of the present invention, the term "pores" is understood to describe the spaces found between and / or within particles, i.e., which are formed by particles when they are packed together in nearest neighbor contact (inter-particle pores), such as in powders or compacts, and / or the void spaces within porous particles (intra-particle pores), and which when saturated with liquid allow the passage of liquid under pressure and / or support the absorption of surface wetting liquids.

[0079] The specific pore volume was measured using mercury intrusion porosimetry using a Micromeritics Autopore V 9620 mercury intrusion porosimeter with a maximum applied pressure of 414 MPa (60 000 psi) of mercury equivalent to a Laplace throat of 0.004 μm. The equilibrium time used for each pressure step was 20 s. The sample material was sealed in a 3 cm 3 The data were corrected for mercury compression, penetrometer expansion, and elastic compression of the sample material using the software Pore-Comp (Gane, PAC, Kettle, JP, Matthews, GP, and Ridgway, CJ, "Void Space Structure of Compressible Polymer Spheres and Consolidated Calcium Carbonate Paper-Coating Formulations", Industrial and Engineering Chemistry Research, 1996, 35 (5), 1996, pp. 1753-1764).

[0080] The total pore volume seen in the cumulative intrusion data is broken down into two regions where the intrusion data drops from 214 μm to about 1 to 4 μm, showing coarse packing of the sample between any strongly contributing aggregate structures. Below these diameters is the inter-particle packing of the particles themselves. If they also have intra-particle pores, this region appears bimodal, and by taking the specific pore volume in pores where the mercury intrusion is finer than the modal turning point (i.e. finer than the bimodal point of inflection), we therefore define the intra-particle specific pore volume. The sum of these three regions yields the overall pore volume of the powder, but is strongly dependent on the original sample compaction / sedimentation of the powder at the coarse pore end of the distribution.

[0081] By taking the first derivative of the cumulative intrusion curve, the pore size distribution based on the equivalent Laplace diameter is revealed, which inevitably includes pore shielding. The differential curve clearly shows the coarse aggregate pore structure region, the inter-particle pore region, and the intra-particle pore region (if any). Knowing the intra-particle pore size range, the remaining inter-particle and inter-aggregate pore volume can be subtracted from the total pore volume to provide the required individual pore volume of the inner pore based on the pore volume per unit mass (specific pore volume). Of course, the same subtraction principle applies to isolate any other pore size region of interest.

[0082] Throughout this document, the term "specific surface area" (in m 2The specific surface area in m2 / g (which is used to define the functionalized calcium carbonate or other material) refers to the specific surface area as determined by using the BET method (using nitrogen as the adsorption gas). Throughout this document, the specific surface area (in m2 / g) is determined using the BET method (using nitrogen as the adsorption gas) known to the skilled person (ISO 9277:2010). 2 The total surface area of ​​the filler material (in m2) is then obtained by multiplying the mass (in g) of the corresponding sample by the specific surface area. 2 count).

[0083] For the purposes of this application, a "water-insoluble" material is defined as a material that, when 100 g of said material is mixed with 100 g of deionized water and filtered on a filter having a pore size of 0.2 μm at 20° C. to recover a liquid filtrate, provides less than or equal to 1 g of recovered solid material after evaporation of 100 g of said liquid filtrate at 95 to 100° C. at ambient pressure. A "water-soluble" material is defined as a material that, when 100 g of said material is mixed with 100 g of deionized water and filtered on a filter having a pore size of 0.2 μm at 20° C. to recover a liquid filtrate, provides greater than 1 g of recovered solid material after evaporation of 100 g of said liquid filtrate at 95 to 100° C. at ambient pressure.

[0084] For the purposes of the present invention, the "solids content" of a liquid composition is a measure of the amount of material remaining after all solvent or water has evaporated. If necessary, the "solids content" of a suspension given in % by weight can be determined within the meaning of the present invention using a Moisture Analyzer HR73 from Mettler-Toledo (T = 120 ° C, automatic switch off 3, standard drying) with a sample size of 5 to 20 g.

[0085] Unless otherwise specified, the term "drying" refers to a process according to which at least a portion of the water is removed from the material to be dried such that a constant weight of the "dried" material obtained is reached at 220°C. The term "dry" material or "dry" composition is to be understood as a material / composition having less than 1.0% by weight of water relative to the weight of the material / composition. The % water (equal to the residual total moisture content) is determined according to the Coulometric Karl Fischer measurement method, wherein the material / composition is heated to 220°C and the water content released as vapor and separated using a nitrogen stream (at 100 ml / min) is determined in a Coulometric Karl Fischer apparatus.

[0086] For the purposes of the present invention, the term "viscosity" or "Brookfield viscosity" refers to Brookfield viscosity. Brookfield viscosity is measured at 100 rpm using a suitable axis of a Brookfield RV-axis set at 25 ° C ± 1 ° C by a Brookfield DV-II + Pro viscometer for this purpose and is specified in mPa s. Based on the technical knowledge of the technician, he / she will select an axis suitable for the viscosity range to be measured from the Brookfield RV-axis set. For example, for a viscosity range between 200 and 800 mPa s, axis number 3 can be used, for a viscosity range between 400 and 1600 mPa s, axis number 4 can be used, for a viscosity range between 800 and 3200 mPa s, axis number 5 can be used, for a viscosity range between 1000 and 2000000 mPa s, axis number 6 can be used, and for a viscosity range between 4000 and 8000000 mPa s, axis number 7 can be used.

[0087] A "suspension" or "slurry" within the meaning of the present invention comprises undissolved solids and water, and optionally further additives, and generally contains a large amount of solids and may therefore have a higher density and be more viscous than the liquid from which it is formed.

[0088] When an indefinite or definite article is used when referring to a singular noun (eg, "a", "an" or "the"), this includes a plural of that noun unless something else is specifically stated.

[0089] When the term "comprising" is used in the present description and claims, other elements are not excluded. For the purposes of the present invention, the term "consisting of" is considered a preferred embodiment of the term "comprising". If hereinafter a group is defined as comprising at least a certain amount of embodiments, this is also considered to disclose a group that preferably consists of only these embodiments.

[0090] Terms such as "obtainable" or "definable" and "obtained" or "definable" can be used interchangeably. This means, for example, that unless the context clearly dictates otherwise, the term "obtained" is not intended to indicate, for example, that an embodiment must be obtained by, for example, a series of steps following the term "obtained", although such a limited understanding is always included as a preferred embodiment by the term "obtained" or "definable".

[0091] Whenever the terms "including" or "having" are used, these terms are intended to be equivalent to "comprising" as defined above. DETAILED DESCRIPTION OF THE INVENTION

[0093] The inventive method for producing a white, UV absorbing, surface-reacted calcium carbonate doped with a titanium species comprises the following steps: a) providing a calcium carbonate-containing material, b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate, c) providing at least one titanium-containing material and d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form an aqueous suspension of a white, UV absorbing, surface-reacted calcium carbonate doped with a titanium species, wherein the calcium carbonate-containing material of step a) and the calcium phosphate of step b) in combination have a calcium ion to phosphate ion molar ratio (Ca 2+ / -) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ), and wherein the at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0094] The preferred embodiments of the white UV-absorbing titanium-doped surface-reacted calcium carbonate of the present invention will be described in more detail below. It should be understood that these embodiments and details also apply to the products of the present invention and their uses and the method of the present invention for preparing the white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0095] Method step a)

[0096] According to step a) of the method of the invention, a material comprising calcium carbonate is provided.

[0097] According to one embodiment, the at least one calcium carbonate-containing material has a content of calcium carbonate of at least 80 wt.-%, preferably 85 wt.-%, more preferably 90 wt.-% and most preferably 95 wt.-%, based on the total weight of the calcium carbonate-containing material. According to another embodiment, the at least one calcium carbonate-containing material consists of calcium carbonate.

[0098] The material comprising calcium carbonate may be selected from natural ground calcium carbonate, precipitated calcium carbonate or mixtures thereof. The natural ground calcium carbonate may preferably be selected from marble, limestone and / or chalk, and / or the precipitated calcium carbonate may preferably be selected from vaterite, calcite and / or aragonite.

[0099] According to one embodiment of the present invention, the material comprising calcium carbonate is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably natural ground calcium carbonate is selected from marble, chalk, limestone and mixtures thereof, and / or the precipitated calcium carbonate is selected from precipitated calcium carbonate having aragonite, vaterite or calcite crystal form and mixtures thereof.

[0100] "Natural ground calcium carbonate" (GCC) is understood to be made from naturally occurring forms of calcium carbonate, mined from sedimentary rocks such as limestone or chalk, or from metamorphic marble rocks, eggshells or shells. Calcium carbonate is known to exist as three types of crystal polymorphs: calcite, aragonite and vaterite. Calcite, the most common crystal polymorph, is considered to be the most stable crystalline form of calcium carbonate. Less common is aragonite, which has a discrete or clustered needle-shaped orthorhombic crystal structure. Vaterite is the rarest calcium carbonate polymorph and is generally unstable. Ground calcium carbonate is almost entirely a calcite polymorph, which is said to be a trigonal-rhombohedral system and represents the most stable form of calcium carbonate polymorphs. In the meaning of the present application, the term "source" of calcium carbonate refers to the naturally occurring mineral material from which calcium carbonate is obtained. The source of calcium carbonate may contain additional naturally occurring components, such as magnesium carbonate, aluminosilicates, etc.

[0101] In general, the grinding of natural ground calcium carbonate can be a dry grinding or wet grinding step, and can be carried out with any conventional grinding device, for example, under conditions such that the pulverization is mainly caused by the impact with the second body, i.e., in one or more of the following: ball mill, rod mill, vibrating mill, roller crusher, centrifugal impact mill, vertical bead mill, grinding mill, pin crusher, hammer mill, crusher, shredder, disperser (de-clumper), scraper cutter or other such equipment known to the technician. If the mineral material containing calcium carbonate comprises a wet-ground mineral material containing calcium carbonate, the grinding step can be carried out under conditions such that autogenous grinding occurs and / or by horizontal ball milling and / or other such methods known to the technician. The mineral material containing ground calcium carbonate thus obtained by wet processing can be rinsed and dehydrated by known methods, for example, by flocculation, filtration or forced evaporation before drying. The subsequent drying step (if necessary) can be carried out in a single step such as spray drying, or in at least two steps. It is also common that such mineral materials undergo a beneficiation step (such as flotation, bleaching or magnetic separation step) to remove impurities.

[0102] According to one embodiment of the present invention, the source of natural ground calcium carbonate (GCC) is selected from marble, chalk, limestone or mixtures thereof. Preferably, the source of ground calcium carbonate is marble, and more preferably magnetic marble. According to one embodiment of the present invention, GCC is obtained by dry grinding. According to another embodiment of the present invention, GCC is obtained by wet grinding and subsequent drying.

[0103] According to one embodiment of the invention, the calcium carbonate comprises one type of natural ground calcium carbonate.According to another embodiment of the invention, the calcium carbonate comprises a mixture of two or more types of natural ground calcium carbonate selected from different sources.

[0104] "Precipitated calcium carbonate" (PCC) in the meaning of the present invention is a synthetic material, usually precipitated after the reaction of carbon dioxide and calcium hydroxide in an aqueous environment or by precipitating calcium ions and carbonate ions such as CaCl and NaCO from a solution to obtain. Another possible way to produce PCC is the lime soda process, or the Solvay process in which PCC is a byproduct of ammonia production. Precipitated calcium carbonate exists in three main crystalline forms: calcite, aragonite and vaterite, and there are many different polymorphs (crystal habits) in each of these crystal forms. Calcite has a trigonal structure, wherein typical crystal habits are such as scalenohedron (S-PCC), rhombohedron (R-PCC), hexagonal prism, oblique hexahedron, colloid (C-PCC), cube and prism (P-PCC). Aragonite is an orthorhombic structure, with double hexagonal prism crystals, and various thin elongated prisms, curved leaves, steep cones, chisel-shaped crystals, branched trees and the typical crystal habits of coral or worm-like forms. Vaterite belongs to the hexagonal crystal system.The obtained PCC slurry can be mechanically dehydrated and dried.

[0105] According to one embodiment of the present invention, the calcium carbonate is precipitated calcium carbonate, preferably comprising aragonite, vaterite or calcite mineralogical crystal forms or mixtures thereof.

[0106] Precipitated calcium carbonate can be prepared by mixing carbon dioxide and at least one H3O + The ion donor treatment is preceded by grinding in the same manner as described above for grinding natural ground calcium carbonate.

[0107] According to one embodiment of the present invention, the calcium carbonate containing material is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-20 μm. 50 (by weight), and / or a weight top cut particle size d of 0.15-1500 μm, preferably 1-600 μm, more preferably 1.5-300 μm and most preferably 2-80 μm 98 (weight).

[0108] The material containing calcium carbonate may have a mass of 1-100 m 2 The specific surface area (BET) of the calcium carbonate-containing material is 1-80 m / g, which is measured using nitrogen and the BET method according to ISO 9277:2010. According to one embodiment, the specific surface area (BET) of the calcium carbonate-containing material is 1-80 m / g. 2 / g, preferably 2-60m 2 / g and more preferably 2-15m 2 / g, which is measured using nitrogen and the BET method according to ISO 9277:2010.

[0109] The material comprising calcium carbonate may also be selected from by-products or waste materials containing materials comprising calcium carbonate. For example, the waste material or by-product may be selected from industrial rejects, recycled waste, waste from the pulp and / or paper industry, industrial gypsum waste or pigmented natural calcareous materials or biogenic minerals, such as eggshells, oyster / clam shells.

[0110] The material comprising calcium carbonate of step a) can be provided in any form such as a solution, a suspension, a slurry, a dispersion, a paste, a powder, a wet cake or in a compressed or granulated form. According to one embodiment, the material comprising calcium carbonate of step a) is provided in a dry form, preferably in a powder form.

[0111] According to another embodiment, the calcium carbonate containing material can be used dry or in the form of an aqueous suspension. According to a preferred embodiment, the calcium carbonate containing material is in the form of an aqueous suspension having a solids content in the range of 1 wt.-% to 95 wt.-%, preferably 10 wt.-% to 90 wt.-%, more preferably 20 wt.-% to 80 wt.-% and most preferably 30 wt.-% to 70 wt.-%, based on the weight of the aqueous suspension.

[0112] The term "aqueous" suspension refers to a system in which the liquid phase comprises water, preferably consists of water. However, the term does not exclude that the liquid phase of the aqueous suspension comprises a small amount of at least one water-miscible organic solvent selected from methanol, ethanol, acetone, acetonitrile, tetrahydrofuran and mixtures thereof. If the aqueous suspension comprises at least one water-miscible organic solvent, the liquid phase of the aqueous suspension comprises an amount of 0.1-40.0 wt.-%, preferably 0.25-30.0 wt.-%, more preferably 0.5-20.0 wt.-% and most preferably 1.0-10.0 wt.-% of at least one water-miscible organic solvent, based on the total weight of the liquid phase of the aqueous suspension. Preferably, the liquid phase of the aqueous suspension consists of water.

[0113] According to a preferred embodiment of the present invention, the aqueous suspension consists of water and a material comprising calcium carbonate.

[0114] Alternatively, the aqueous suspension of the material comprising calcium carbonate may include additional additives such as dispersants. Suitable dispersants may be selected from polyphosphates, and particularly tripolyphosphates. Another suitable dispersant may be selected from homopolymers or copolymers or mixtures thereof based on polycarboxylates such as acrylic acid, methacrylic acid, maleic acid, fumaric acid or itaconic acid and acrylamide. The homopolymer or copolymer of polycarboxylates may be completely or partially neutralized, such as at least 70%, or at least 80% or at least 90% of the acid groups are neutralized. Neutralization means that the proton of the carboxylic acid is exchanged with another cation such as sodium and / or calcium ions. According to a preferred embodiment, the homopolymer or copolymer of polycarboxylates is completely neutralized and most preferably completely neutralized by sodium and / or calcium ions. The completely or partially neutralized homopolymer or copolymer of acrylic acid is particularly preferred. Most preferably, it is a homopolymer or copolymer of acrylic acid completely neutralized by sodium and / or calcium ions. The weight average molecular weight M of such a product is preferably 100-1000 wt %; w Preferably in the range of 2000-15000 g / mol, wherein the weight average molecular weight M w 3000-7000 g / mol or 3500-6000 g / mol is particularly preferred. According to an exemplary embodiment, the dispersant is a dispersant having a weight average molecular weight M w It is 2000-15000 g / mol, preferably 3000-7000 g / mol and most preferably 3500-6000 g / mol of sodium polyacrylate.

[0115] According to one embodiment of the present invention, the calcium carbonate-containing material provided in process step a) is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably an aqueous suspension of natural ground calcium carbonate and / or precipitated calcium carbonate having a solids content in the range of 1 wt.-% to 95 wt.-%, preferably 10 wt.-% to 90 wt.-%, more preferably 20 wt.-% to 80 wt.-% and most preferably 30 wt.-% to 70 wt.-%, based on the weight of the aqueous suspension.

[0116] According to one embodiment of the present invention, the calcium carbonate-containing material is preferably natural ground calcium carbonate and / or precipitated calcium carbonate, and more preferably natural ground calcium carbonate and / or precipitated calcium carbonate provided in dry form.

[0117] Method step b)

[0118] According to step b) of the method of the present invention, a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate is provided. The calcium carbonate-containing material of step a) and the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ).

[0119] For the purposes of the present invention, the term "monocalcium phosphate" refers to an inorganic compound having the chemical formula Ca(H2PO4)2 and its hydrates. Examples of monocalcium phosphate are anhydrous monocalcium phosphate (Ca(H2PO4)2) or monocalcium phosphate monohydrate (Ca(H2PO4)2·H2O).

[0120] "Dicalcium phosphate" in the meaning of the present invention refers to an inorganic compound with the chemical formula CaHPO4 and its hydrates. Examples of dicalcium phosphate are anhydrous dicalcium phosphate (CaHPO4) such as the mineral monetite, dicalcium phosphate hemihydrate (CaHPO4.0.5H2O), or dicalcium phosphate dihydrate (CaHPO4.2H2O) such as the mineral calcite.

[0121] According to one embodiment, the calcium phosphate provided in step b) of the method of the present invention is selected from anhydrous monocalcium phosphate (Ca(H2PO4)2), monocalcium phosphate monohydrate (Ca(H2PO4)2·H2O), anhydrous dicalcium phosphate (CaHPO4), dicalcium phosphate hemihydrate (CaHPO4·0.5H2O), dicalcium phosphate dihydrate (CaHPO4·2H2O), or a mixture thereof, preferably the calcium phosphate provided in step b) of the method of the present invention is selected from anhydrous dicalcium phosphate (CaHPO4), dicalcium phosphate hemihydrate (CaHPO4·0.5H2O), dicalcium phosphate dihydrate (CaHPO4·2H2O), or a mixture thereof, and more preferably the calcium phosphate provided in step b) of the method of the present invention is dicalcium phosphate dihydrate (CaHPO4·2H2O).

[0122] According to one embodiment, the calcium phosphate provided in step b) of the method of the present invention is dicalcium phosphate, preferably selected from anhydrous dicalcium phosphate (CaHPO 4 ), dicalcium phosphate hemihydrate (CaHPO 4 .0.5H 2 O), dicalcium phosphate dihydrate (CaHPO 4 .2H 2 O), or a mixture thereof, and more preferably the dicalcium phosphate is dicalcium phosphate dihydrate (CaHPO 4 .2H 2 O).

[0123] According to one embodiment, the calcium carbonate-containing material of step a) and the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.9:1 to 75:1, preferably 2:1 to 50:1, more preferably 2.2:1 to 25:1 and most preferably 2.5:1 to 10:1. 2+ :PO4 3- ).

[0124] According to one embodiment, the calcium phosphate of step b) is dicalcium phosphate dihydrate and is provided in an amount of 1.7-230 wt.-%, preferably 2.3-191 wt.-%, more preferably 3.5-172 wt.-% and most preferably 19-115 wt.-%, based on the total weight of the calcium carbonate-containing material of step a).

[0125] According to another embodiment, the calcium phosphate of step b) is dicalcium phosphate hemihydrate and is provided in an amount of 1.7-230 wt.-%, preferably 2.3-191 wt.-%, more preferably 3.5-172 wt.-% and most preferably 19-115 wt.-%, based on the total weight of the calcium carbonate-containing material of step a).

[0126] According to another embodiment, the calcium phosphate of step b) is anhydrous dicalcium phosphate and is provided in an amount of 1.4-181 wt.-%, preferably 1.8-151 wt.-%, more preferably 2.8-136 wt.-% and most preferably 15-91 wt.-%, based on the total weight of the calcium carbonate-containing material of step a).

[0127] According to another embodiment, the calcium phosphate of step b) is anhydrous monocalcium phosphate and is provided in an amount of 1.2-94 wt.-%, preferably 1.6-84 wt.-%, more preferably 2.4-78 wt.-% and most preferably 12-59 wt.-%, based on the total weight of the calcium carbonate-containing material of step a).

[0128] According to one embodiment, the calcium phosphate of step b) is monocalcium phosphate monohydrate and is provided in an amount of 1.3-100 wt.-%, preferably 1.7-90 wt.-%, more preferably 2.5-84 wt.-% and most preferably 13-63 wt.-%, based on the total weight of the calcium carbonate-containing material of step a).

[0129] According to another embodiment, the calcium phosphate of step b) is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-40 μm. 50 Additionally or alternatively, the calcium phosphate of step b) may be in the form of particles having a weight top cut particle size d of 0.15-1500 μm, preferably 1-600 μm, more preferably 1.5-300 μm and most preferably 2-110 μm. 98 (weight).

[0130] According to one embodiment, the calcium phosphate of step b) is dicalcium phosphate and is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-40 μm. 50(by weight), and / or a weight top cut particle size d of 0.15-1500 μm, preferably 1-600 μm, more preferably 1.5-300 μm and most preferably 2-110 μm 98 (weight).

[0131] The calcium phosphate of step b) may have a m 2 / g of specific surface area (BET), which is measured using nitrogen and the BET method according to ISO9277:2010. According to one embodiment, the specific surface area (BET) of the calcium phosphate of step b) is 0.2-100m 2 / g, preferably 0.3-60m 2 / g and more preferably 0.5-30m 2 / g, which is measured using nitrogen and the BET method according to ISO 9277:2010.

[0132] The calcium phosphate of step b) may be provided in any form such as a suspension, slurry, dispersion, paste, powder, wet cake or in compressed or granulated form. According to one embodiment, the calcium phosphate of step b) is provided in dry form, preferably in powder form.

[0133] According to another embodiment, the calcium phosphate of step b) is provided in the form of an aqueous suspension, preferably with a solid content in the range of 1 to 90 wt %, more preferably 3-60 wt %, even more preferably 5-40 wt % and most preferably 10-25 wt %, based on the weight of the aqueous suspension. According to a preferred embodiment of the present invention, the aqueous suspension consists of water and the calcium phosphate of step b). Alternatively, the aqueous suspension of the calcium phosphate of step b) may include other additives such as dispersants. Another suitable dispersant may be selected from homopolymers or copolymers or mixtures thereof based on polycarboxylic acids or their salts and acrylamide such as acrylic acid, methacrylic acid, maleic acid, fumaric acid or itaconic acid. Acrylic homopolymers or copolymers are particularly preferred. Homopolymers or copolymers may be completely in acidic form or partially or completely neutralized. The weight average molecular weight M of such a product is preferably 0.05 wt %. w Preferably in the range of 2000-15000 g / mol, wherein the weight average molecular weight M w 3000-7000 g / mol or 3500-6000 g / mol is particularly preferred. According to an exemplary embodiment, the dispersant is a dispersant having a weight average molecular weight M w It is 2000-15000 g / mol, preferably 3000-7000 g / mol and most preferably 3500-6000 g / mol of sodium polyacrylate.

[0134] Monocalcium phosphate and dicalcium phosphate are commercially available or can be produced on site, for example by treating calcium hydroxide or calcium carbonate with phosphoric acid.

[0135] According to one embodiment, the calcium phosphate provided in process step b) is dicalcium phosphate. The dicalcium phosphate may be produced in situ or in a separate process.

[0136] According to one embodiment, a separate method for producing dicalcium phosphate comprises the following steps:

[0137] i) providing a source of calcium ions other than dicalcium phosphate, preferably providing a material comprising calcium carbonate, more preferably providing natural ground calcium carbonate,

[0138] ii) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof, and

[0139] iii) contacting the calcium ion source of step i) and the phosphate ion source of step ii) in the presence of water to form dicalcium phosphate,

[0140] The calcium ion source of step i) and the phosphate ion source of step ii) are provided in combination at a molar ratio of calcium ion to phosphate ion of 1:2 to 5:1.

[0141] The calcium ion source may be selected from materials comprising calcium carbonate, calcium oxide, calcium hydroxide, calcium chloride, calcium nitrate, calcium chlorate, calcium bromide, calcium iodide, calcium acetate, calcium sulfate, calcium citrate, or mixtures thereof. According to one embodiment, the calcium ion source excludes calcium phosphate.

[0142] According to one embodiment, the calcium ion source is selected from a material comprising calcium carbonate, calcium chlorate, calcium bromide, calcium iodide, calcium acetate, calcium sulfate, or a mixture thereof, preferably the calcium ion source is selected from a material comprising calcium carbonate, calcium acetate, calcium sulfate, or a mixture thereof and most preferably the calcium ion source is a material comprising calcium carbonate. According to a preferred embodiment, the calcium ion source is a material comprising calcium carbonate, preferably selected from natural ground calcium carbonate, precipitated calcium carbonate, dolomite, or a mixture thereof, more preferably selected from natural ground calcium carbonate, precipitated calcium carbonate, or a mixture thereof and most preferably the material comprising calcium carbonate is natural ground calcium carbonate. The material comprising calcium carbonate has been described in step a).

[0143] The source of calcium ions may also be selected from byproducts or waste materials containing calcium compounds in an acid-soluble form. For example, the waste materials or byproducts may be selected from industrial rejects, recycled waste, waste from the pulp and / or paper industry, industrial gypsum waste, or pigment-discolored natural calcified materials or biogenic minerals, such as eggshells, oyster / clam shells.

[0144] The calcium ion source may be provided in solid form or as an aqueous suspension or solution.

[0145] According to one embodiment, the calcium ion source is provided in the form of a solution, preferably comprising the calcium ion source in an amount of 0.1-99 wt. %, more preferably in an amount of 1-80 wt. %, even more preferably in an amount of 10-50 wt. % and most preferably in an amount of 20-40 wt. %, based on the total weight of the aqueous solution. According to another embodiment, the calcium ion source is provided in the form of an aqueous suspension, preferably comprising the calcium ion source in an amount of 0.1-99 wt. %, preferably in an amount of 1-80 wt. %, more preferably in an amount of 10-50 wt. % and most preferably in an amount of 20-40 wt. %, based on the total weight of the aqueous suspension.

[0146] According to one embodiment, the source of calcium ions provided in step i) of the above-mentioned separate process for producing dicalcium phosphate is the same as the material comprising calcium carbonate provided in step a) of the process of the present invention.

[0147] According to another embodiment, dicalcium phosphate is produced in situ in the method of the present invention. Therefore, method steps b) and d) of the method of the present invention are replaced by method steps ii) and iii) described above, i.e. method steps b) and d) are replaced by following steps B) and D):

[0148] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof, and

[0149] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate,

[0150] wherein the molar ratio of calcium ions to phosphate ions (Ca) is in the range of 1.75:1 to 100:1. 2+ :PO4 3- ) provide the calcium carbonate-containing material of step a) and the phosphate ion source of step b).

[0151] Thus, an in-situ method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species comprises the following steps:

[0152] a) providing a material comprising calcium carbonate,

[0153] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof,

[0154] c) providing at least one substance comprising titanium,

[0155] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0156] e) grinding the aqueous suspension of step D) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0157] wherein the calcium carbonate-containing material of step a) and the phosphate ion source of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0158] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0159] Unless otherwise indicated, the following explanations and embodiments apply both to the separate process for producing dicalcium phosphate and to the in situ process for producing a white, UV-absorbing, surface-reacted aqueous suspension of calcium carbonate doped with titanium species, wherein the dicalcium phosphate is formed in situ.

[0160] According to one embodiment, the phosphate ion source is phosphoric acid. According to another embodiment, the phosphate ion source is a salt of phosphoric acid, such as a non-hydrogenated salt, a monohydrogen salt (preferably Na2HPO4) or a dihydrogen salt of phosphoric acid, preferably a dihydrogenated salt of phosphoric acid, more preferably selected from NaH2PO4, KH2PO4, LiH2PO4, NH4H2PO4, Ca(H2PO4)2, Mg(H2PO4)2 and mixtures thereof. The phosphate ion source can also be a mixture of phosphoric acid and its salts. According to one embodiment, the phosphate ion source is a mixture of phosphoric acid and its non-hydrogenated salt, a monohydrogen salt (preferably Na2HPO4) or a dihydrogen salt, preferably a mixture of phosphoric acid and its dihydrogen salt, and more preferably a mixture of phosphoric acid and a dihydrogen salt selected from NaH2PO4, KH2PO4, LiH2PO4, NH4H2PO4, Ca(H2PO4)2, Mg(H2PO4)2 and mixtures thereof. The technician will understand that the anhydrous form and hydrates of the above-mentioned salts of phosphoric acid can be used.

[0161] In addition, the phosphate ion source may include other suitable phosphate ion sources. For example, the phosphate ion source may include a dibasic salt or a tribasic salt of phosphoric acid.

[0162] The source of phosphate ions may also be obtained from byproducts or waste materials containing phosphoric acid, its dihydrogen salt, or mixtures thereof.

[0163] The source of phosphate ions may be provided in solid form or in the form of an aqueous suspension or aqueous solution.

[0164] According to one embodiment, the phosphate ion source is provided in the form of a solution, preferably in an amount of 0.1-99 wt. %, more preferably in an amount of 1-80 wt. %, even more preferably in an amount of 10-50 wt. % and most preferably in an amount of 20-40 wt. %, based on the total weight of the aqueous solution. According to another embodiment, the phosphate ion source is provided in the form of an aqueous suspension, preferably in an amount of 0.1-99 wt. %, preferably in an amount of 1-80 wt. %, more preferably in an amount of 10-50 wt. % and most preferably in an amount of 20-40 wt. %, based on the total weight of the aqueous suspension.

[0165] According to one embodiment, the phosphate ion source is provided in solid form, preferably in powder form.The powder may contain a small amount of moisture, for example up to 1 wt.-%, based on the total weight of the powder.

[0166] According to one embodiment, in a separate process for producing dicalcium phosphate comprising steps i) to iii), the calcium ion to phosphate ion molar ratio (Ca 2+) is 2:3 to 2:1, preferably 3:4 to 3:2, more preferably 5:6 to 4:3, still more preferably 10:11 to 11:10 and most preferably about 1:1. 2+ :PO4 3- ) provide a source of calcium ions in step i) and a source of phosphate ions in step ii).

[0167] According to one embodiment, in an in situ process comprising steps a), b), c), d) and e), wherein dicalcium phosphate is formed in situ, the calcium ion to phosphate ion molar ratio (Ca 2+) is from 1.9:1 to 75:1, preferably from 2:1 to 50:1, more preferably from 2.2:1 to 25:1 and most preferably from 2.5:1 to 10:1. 2+ :PO4 3- ) provide the calcium carbonate-containing material of step a) and the phosphate ion source of step b).

[0168] According to one embodiment, in a separate process for producing dicalcium phosphate comprising steps i) to iii), process step iii) is carried out at a pH value below 5, preferably at a pH value of 1.0-4.9, more preferably 1.1-4.7, even more preferably 1.8-4.2 and most preferably 2.2-4.0. The pH value can be controlled by the amount of the source of phosphate ions.

[0169] Method step c)

[0170] According to step c) of the method of the invention, at least one substance comprising titanium is provided.

[0171] According to one embodiment of the present invention, the at least one substance containing titanium is selected from titanium salts, titanium hydroxide, titanium dioxide, and mixtures thereof.

[0172] According to a preferred embodiment of the present invention, the substance containing titanium is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the substance containing titanium is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

[0173] A "titanium salt" within the meaning of the present invention is a chemical compound consisting of an ionic combination of cations (positively charged ions) and anions (negatively charged ions) comprising titanium such that the product is electrically neutral (has no net charge).

[0174] The anion may be an inorganic anion such as chloride ion (Cl - ), bromide ion (Br - ), fluoride ion (F - ), iodide ion (I - ), or organic anions such as acetate (CH3CO - 2), sulfate radical (SO 2- 4), or nitrate (NO3 - ).

[0175] The cation may be a titanium cation such as Ti 2+ 、Ti 3+ or Ti 4+ cation.

[0176] Examples of suitable titanium salts are titanium bromides such as TiBr4 or TiBr3, titanium fluorides such as TiF4 or TiF3, titanium iodide (TiI4), titanium chloride (TiCl4), titanium oxysulfate (TiOSO4), titanium sulfate (Ti2(SO4)3), titanium nitrate (Ti(NO3)4) or titanium acetate (Ti(C2H3O2)4). The titanium salt may be an amorphous salt or a hydrate salt.

[0177] As used herein, "hydrate" is an inorganic salt that contains water molecules in a certain ratio that are incorporated as an integral part of the crystal. Depending on the number of water molecules per formula unit of the salt, the hydrate can be designated as a monohydrate, dihydrate, trihydrate, tetrahydrate, pentahydrate, hexahydrate, heptahydrate, octahydrate, nonahydrate, decahydrate, hemihydrate, etc.

[0178] "Titanium hydroxide" within the meaning of the present invention is a compound comprising a compound having the formula OH - A chemical compound containing a diatomic anion of a metal. The hydroxide ion consists of oxygen and hydrogen atoms held together by a single covalent bond and carries a negative charge. Examples of suitable titanium hydroxides are Ti(OH)4 or Ti(OH)3.

[0179] "Titanium dioxide" within the meaning of the present invention is a chemical compound comprising titanium and oxygen, wherein the oxygen has an oxidation number (II). Examples of suitable titanium dioxides are TiO2, TiO, Ti2O3, Ti3O or Ti2O, delta-TiO x Where x = 0.68–0.75 or Ti n O 2n-1 Wherein n ranges from 3 to 9 (inclusive).

[0180] According to a preferred embodiment, the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof. According to a preferred embodiment, the titanium-containing substance is titanium oxysulfate, also known as titanium oxysulfate.

[0181] The substance containing titanium may be a water-soluble or water-insoluble substance.

[0182] According to one embodiment, at least one substance comprising titanium is provided in an amount of 0.1-20 wt. % titanium element, preferably 0.5-15 wt. %, more preferably 1.0-10 wt. % and most preferably 2.5-7.5 wt. %, based on the total weight of the material comprising calcium carbonate. The term "titanium element" in the meaning of the present invention refers to the weight of titanium in the substance comprising titanium, assuming that titanium is present as Ti 0 Existence is also referred to as elemental titanium in substances containing titanium.

[0183] According to another embodiment, the at least one titanium containing substance is provided in an amount of 0.1-20 mol % titanium, preferably 0.5-15 mol %, more preferably 1.0-10 mol % and most preferably 2.5-7.5 mol %, based on the total amount of calcium carbonate containing material.

[0184] The at least one substance comprising titanium may be provided in the form of a solution, a suspension or as a dry material.

[0185] According to one embodiment, at least one substance comprising titanium is provided as a dry material. The dry material may be in the form of a powder, flakes, pellets, etc., and is most preferably in the form of a powder.

[0186] According to another embodiment, the at least one substance comprising titanium is provided in the form of a solution or a suspension. Preferably, the solution or suspension comprises the at least one substance comprising titanium in an amount of 0.01-10 wt. %, preferably in an amount of 0.1-8.0 wt. %, more preferably in an amount of 0.4-5.0 wt. % and most preferably in an amount of 0.8-2.0 wt. %, based on the total weight of the solution or suspension.

[0187] The solution or suspension may be an aqueous solution or suspension, or an organic solution or suspension. Alternatively, the solution or suspension may comprise both water and an organic solvent, the organic solvent being miscible with water in any ratio, preferably a water:solvent ratio of 100:0.1 to 100:200, preferably 100:1 to 100:150, more preferably 100:5 to 100:120 and most preferably 100:10 to 100:100, based on the weight of water and the dry weight of the solvent. Possible organic solvents of the present invention are, for example, methanol, ethanol, ethylene glycol, glycerol, acetone or propanol.

[0188] According to a preferred embodiment, the solution or suspension is an aqueous solution or suspension comprising water and a substance comprising titanium, preferably consisting of water and a substance comprising titanium.

[0189] Method steps d) and e)

[0190] According to step d) of the process of the present invention, the calcium carbonate-containing material of step a) is treated with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension.

[0191] According to step e), the aqueous suspension of step d) is ground at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species.

[0192] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0193] Unless otherwise indicated, the following explanations and embodiments also apply to the in-situ process for producing a white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species as defined above comprising steps a), B), c), D) and e), wherein dicalcium phosphate is formed in situ. The skilled person will understand that in said case, process step B) corresponds to process step b) and process step D) corresponds to process step d).

[0194] According to step d) of the process of the present invention, the calcium carbonate-containing material of step a) is treated with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension.

[0195] In case of an in-situ process, the calcium carbonate-comprising material of step a) is treated in step D) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate.

[0196] The treatment step d) or D) is preferably carried out under mixing conditions. Suitable mixing methods are known to the skilled person. Examples of suitable mixing methods are shaking, mixing, stirring, agitation, ultrasound or inducing turbulence or laminar flow by means of, for example, baffles or thin sheets. Suitable mixing equipment is known to the skilled person and can be selected, for example, from agitators such as rotor-stator systems, blade stirrers, propeller stirrers, turbine stirrers or anchor stirrers, static mixers such as pipelines comprising baffles or thin sheets. According to an exemplary embodiment of the present invention, a rotor-stator stirrer system is used. The skilled person will adjust the mixing conditions such as mixing speed and temperature according to his process equipment.

[0197] The treatment step d) or D) may be performed for at least 1 minute, preferably for at least 5 minutes, more preferably for at least 10 minutes and most preferably for at least 15 minutes.

[0198] The calcium carbonate-containing material of step a) can be treated with the calcium phosphate of step b) by providing an aqueous suspension containing the calcium carbonate material and adding the calcium phosphate of step b). The calcium phosphate of step b) can be added to the suspension as a concentrated solution or a more diluted solution. As an alternative, the calcium carbonate-containing material can also be treated with the calcium phosphate of step b) by adding the calcium carbonate-containing material to the solution of the calcium phosphate of step b).

[0199] In the case of an in-situ method, the material comprising calcium carbonate of step a) can be treated with the source of phosphate ions of step B) by providing an aqueous suspension of the material comprising calcium carbonate and adding the source of phosphate ions of step B). The source of phosphate ions of step B) can be added to the suspension as a concentrated solution or a more dilute solution. As an alternative, the material comprising calcium carbonate can also be treated with the source of phosphate ions of step B) by adding the material comprising calcium carbonate to a solution of the source of phosphate ions of step B).

[0200] According to one embodiment, the raw materials, i.e. the calcium carbonate-containing material of step a) and the calcium phosphate of step b), are at room temperature, i.e. they have a temperature of 20° C.±2° C. The raw materials may be mixed in any order. According to one embodiment, step d) comprises the following steps:

[0201] d1) mixing the calcium carbonate-containing material of step a) with water, and

[0202] d2) mixing the calcium phosphate from step b) with the mixture from step d1).

[0203] According to another embodiment, step d) comprises the following steps:

[0204] d1') mixing the calcium phosphate of step b) with water, and

[0205] d2') mixing the calcium carbonate-containing material of step a) with the mixture of step d1'.

[0206] According to yet another embodiment, the calcium carbonate containing material of step a), the calcium phosphate of step b) and water are mixed simultaneously.

[0207] According to another embodiment, the raw materials, i.e. the calcium carbonate-containing material of step a) and the phosphate ion source of step B) exhibit room temperature, i.e. they have a temperature of 20° C.±2° C. The raw materials may be mixed in any order. According to one embodiment, step D) comprises the following steps:

[0208] D1) mixing the calcium carbonate-containing material of step a) with water, and

[0209] D2) mixing the phosphate ion source of step B) with the mixture of step D1).

[0210] According to another embodiment, step D) comprises the following steps:

[0211] D1') mixing the phosphate ion source of step B) with water, and

[0212] D2') mixing the calcium carbonate-containing material of step a) with the mixture of step D1'.

[0213] According to yet another embodiment, the calcium carbonate containing material of step a), the phosphate ion source of step B) and water are mixed simultaneously.

[0214] Depending on the amount of water introduced during process steps a) and b) or B), additional water may be introduced, for example, during process step d) or D), in order to control and / or maintain and / or achieve a desired solid content or Brookfield viscosity of the aqueous suspension obtained. According to one embodiment, the aqueous suspension formed in step d) or D) has a solid content of 1-95% by weight, preferably 3-75% by weight, more preferably 5-50% by weight, even more preferably 7-30% by weight, still more preferably 9-25% by weight and most preferably 10-20% by weight, based on the total weight of the aqueous suspension. The Brookfield viscosity of the aqueous suspension obtained may be 10-10000 mPa·s, preferably 50-5000 mPa·s, more preferably 100-1000 mPa·s and most preferably 200-800 mPa·s.

[0215] According to one embodiment of the invention, in step d), the pH of the aqueous suspension obtained is at least 4.2, preferably 4.5-14, more preferably 4.7-13.5, more preferably 5-13, even more preferably 5.5-12.5 and most preferably 6-12 and most preferably at pH 6.0-8.0.

[0216] According to one embodiment of the present invention, step d) is carried out at a temperature of 10-100°C, preferably 15-80°C, more preferably 20-50°C and most preferably 20±2°C.

[0217] The process of step d) or D) can be carried out as a continuous process or as a batch process, preferably as a batch process.

[0218] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0219] According to a preferred embodiment of the present invention, the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) but before step e) and most preferably, during step d).

[0220] If the at least one titanium-containing substance of step c) is added after step d), the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate is still present in the solution. If the at least one titanium-containing substance of step c) is added before and / or during step d), the at least one titanium-containing substance of step c) is still present in the solution when the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate is added.

[0221] Alternatively, in the case of an in-situ process, the at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0222] According to a preferred embodiment of the present invention, the at least one titanium-containing substance of step c) is added before and / or during and / or after step D) but before step e), and most preferably, during step D) in case of an in situ process.

[0223] If the at least one titanium-containing substance of step c) is added after step D), the dicalcium phosphate obtained in step D) is still present in solution. If the at least one titanium-containing substance of step c) is added before and / or during step D), the at least one titanium-containing substance of step c) is still present in solution when the dicalcium phosphate is formed in step D).

[0224] During the inventive method, the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) or the dicalcium phosphate obtained in step D) and at least one substance comprising titanium are present simultaneously in a composition comprising a material comprising calcium carbonate and / or a surface-reacted calcium carbonate. Without wishing to be bound by theory, the inventors believe that the simultaneous presence of a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate and at least one substance comprising titanium leads to doping of the surface-reacted calcium carbonate with the titanium substance. Thus, this method is different from mixing the already formed surface-reacted calcium carbonate with at least one substance comprising titanium in the absence of a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate, which results in only mixing (even in aqueous suspension) and will not result in doped materials.

[0225] According to one embodiment of the invention, in a first step the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) is added to the material comprising calcium carbonate of step a) and thereafter the substance comprising titanium of step c) is added.

[0226] According to another embodiment of the invention, in a first step the material comprising titanium of step c) is added to the material comprising calcium carbonate of step a) and thereafter the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) is added.

[0227] According to another embodiment of the present invention, the substance comprising titanium of step c) is added to the calcium carbonate comprising material of step a) together with the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b).

[0228] According to one embodiment of the invention, in a first step the material comprising calcium carbonate of step a) is added with a phosphate ion source selected from phosphoric acid, its salts or mixtures thereof of step b) and thereafter with a substance comprising titanium of step c).

[0229] According to another embodiment of the invention, in a first step to the material comprising calcium carbonate of step a) is added the substance comprising titanium of step c) and thereafter the source of phosphate ions selected from phosphoric acid, its salts or mixtures thereof of step B) is added.

[0230] According to another embodiment of the present invention, the substance comprising titanium of step c) is added to the calcium carbonate comprising material of step a) together with the source of phosphate ions selected from phosphoric acid, salts thereof or mixtures thereof of step B).

[0231] According to one embodiment of the present invention, the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate in step b) or the phosphate ion source selected from phosphoric acid, its salt or mixture thereof in step B) and / or at least one substance containing titanium in step c) are added in solid form or in solution form. Preferably, the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate in step b) or the phosphate ion source selected from phosphoric acid, its salt or mixture thereof in step B) and / or at least one substance containing titanium in step c) are added in solution form. More preferably, the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate in step b) or the phosphate ion source selected from phosphoric acid, its salt or mixture thereof in step B) and at least one substance containing titanium in step c) are added in solution form.

[0232] The calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) or the phosphate ion source selected from phosphoric acid, its salts or mixtures thereof of step B) and the at least one substance comprising titanium of step c) can be provided in the form of separate solutions and / or in the form of combined solutions. According to one embodiment, the material comprising calcium carbonate is treated in step d) or D) with a solution comprising the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) or the phosphate ion source selected from phosphoric acid, its salts or mixtures thereof of step B) and the at least one substance comprising titanium of step c).

[0233] The compounds of step a) and / or b) or B) and / or c) can be added in one or several portions. According to one embodiment, each of the compounds can be added individually using a first solution or portion containing a first portion of the compound and then a second solution or portion containing the remaining portion of the compound. The first solution or portion may contain less than or equal to 50% by weight of the compound, preferably less than or equal to 40% by weight, more preferably less than or equal to 30% by weight and most preferably less than or equal to 20% by weight, based on the total amount of the compound. For example, the first solution or portion may contain 0.1-50% by weight of the compound, preferably 1-40% by weight, more preferably 5-30% by weight and most preferably 10-20% by weight, based on the total amount of the compound.

[0234] According to process step e) of the process of the invention, the aqueous suspension of step d) is ground at a pH value of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species.

[0235] In general, process step e) can be carried out with any conventional grinding apparatus, for example, under conditions such that the refining is mainly caused by impact with the second body, for example in one or more of the following: ball mill, rod mill, vibrating mill, sand mill, roll crusher, centrifugal impact mill, vertical bead mill, attritor, centrifugal mill, hammer mill, crusher, pulverizer, disperser, scraper cutter or other such equipment known to the skilled person. Grinding step e) can also be carried out under conditions such that spontaneous grinding occurs and / or by horizontal and or vertical ball milling and / or other such methods known to the skilled person.

[0236] According to one embodiment, step e) is carried out in a ball mill, a rod mill, a vibration mill, a centrifugal impact mill, a vertical bead mill, an attritor, a sand mill or a combination thereof. Preferably, the grinding step e) can be carried out in a ball mill.

[0237] It should be noted that method step e) can be carried out in at least one grinding device, ie a series of grinding devices can also be used.

[0238] According to one embodiment, method step e) is carried out in one grinding device. According to another embodiment, method step e) is carried out in a series of grinding devices, preferably in a series of two, three, four or five grinding devices. According to one embodiment, method step e) is carried out in a series of grinding devices, wherein additional calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate is added after the first grinding device and before at least one subsequent grinding device of the series of grinding devices. For example, method step e) is carried out in a series of two grinding devices, and additional calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate is added after the first grinding device and before the second grinding device. According to another example, method step e) is carried out in a series of three grinding devices, and additional calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate is added after the first grinding device and before the second grinding device and after the second grinding device and before the third grinding device.

[0239] The inventive method requires that step e) be carried out at a pH of at least 4.2 in order to ensure that calcium salts other than monocalcium phosphate and dicalcium phosphate and calcium phosphates selected from monocalcium phosphate and / or dicalcium phosphate are converted into surface-reacted calcium salt particles during method step e). According to one embodiment, method step e is carried out at a pH of 4.5-14, preferably 4.7-13.5, more preferably 5-13, even more preferably 5.5-12.5 and most preferably 6-12 and most preferably at a pH of 6.0-8.0. If necessary, the pH of the aqueous suspension obtained in step d) and / or D) can be adjusted by all methods known in the art. According to one embodiment, the pH of the aqueous suspension obtained in step d) or D) is adjusted to a pH of at least 4.2 by adding potassium hydroxide, sodium hydroxide, ammonium hydroxide or a mixture thereof.

[0240] Depending on the amount of water introduced during process steps a), b) or B), c) and d) or D), additional water may be introduced, for example, during process step e) in order to control and / or maintain and / or achieve a desired solid content or Brookfield viscosity of the aqueous suspension obtained. According to one embodiment, process step e) is carried out with a solid content of 1-95% by weight, preferably 3-75% by weight, more preferably 5-50% by weight, even more preferably 7-30% by weight, still more preferably 9-25% by weight and most preferably 10-20% by weight, based on the total weight of the aqueous suspension. The Brookfield viscosity of the aqueous suspension may be 10-10000 mPa·s, preferably 50-5000 mPa·s, more preferably 100-1000 mPa·s and most preferably 200-800 mPa·s.

[0241] Process step e) can be carried out at room temperature, i.e. at 20°C ± 2°C, or at other temperatures. According to one embodiment of the present invention, step e) is carried out at a temperature of 10-100°C, preferably 15-80°C, more preferably 20-50°C and most preferably 20°C ± 2°C. Heat can be introduced by internal shearing or by external sources or a combination thereof. If desired, step e) can be carried out under cooling conditions using methods and equipment known in the art.

[0242] According to one embodiment of the present invention, step e) is carried out at a starting temperature of 0-110°C, preferably 10-100°C, more preferably 15-80°C, more preferably 20-50°C and most preferably 20°C±2°C.

[0243] If the inventive process is performed as an in situ process as defined above comprising steps a), B), c), D) and e), step e) is preferably performed at a temperature of 0-35°C, more preferably 5-30°C and most preferably 10-25°C). According to one embodiment, in the in situ process as defined above comprising steps a), B), c), D) and e), step e) is performed at a starting temperature of 0-35°C, preferably 5-30°C and most preferably 10-25°C.

[0244] According to one embodiment, step e) is performed for a time period ranging from 10 seconds to 5 hours, preferably from 30 seconds to 2 hours, more preferably from 1 minute to 60 minutes, even more preferably from 5 to 40 minutes and most preferably from 10 minutes to 30 minutes.

[0245] Process step e) can be carried out at any suitable specific grinding energy (SGE) by first simultaneously recording the power consumption (P) of the grinding apparatus in kW and the volume flow rate (v s )(in m 3 / h) and is indicated in the corresponding monitoring display. In addition, the total solids (TS) content of the feed slurry (in weight %) is determined using a moisture analyzer HR73 from Mettler-Toledo (T = 120 ° C, automatic shut-off 3, standard drying) using a sample size of 5 to 20 g. The density of water (ρ w ) is 1.00T / m 3 and the density of the applied dry calcium carbonate / marble / chalk (ρ c ) is 2.71T / m 3 , then SGE can be calculated as a function of given quantities, as expressed in equations (1), (2) and (3).

[0246] SGE=P / ((TS)·m s ) Equation (1)

[0247] m s =ρ s ·v s Equation (2)

[0248] ρ s =[ρ c ·ρ w ] / [ρ c ·(1-(TS))+ρ w ·(TS)] Equation (3)

[0249] According to one embodiment, step e) is performed with a specific grinding energy of 50-500 kWh / dry metric ton of final product, preferably 70-450 kWh / dry metric ton of final product, more preferably 150-350 kWh / dry metric ton of final product and most preferably 200-300 kWh / dry metric ton of final product.

[0250] According to one embodiment, method step e) is carried out until the fraction of surface-reacted calcium salt particles having a particle size of less than 4 μm is greater than 10% by volume, preferably greater than 20% by volume, more preferably greater than 30% by volume and most preferably greater than 50% by volume, based on the total volume of the surface-reacted calcium salt particles.

[0251] According to one embodiment of the present invention, process step e) can be carried out as a batch process, a semi-continuous process or a continuous process. According to a preferred embodiment of the present invention, process step e) is carried out as a continuous process.

[0252] According to a preferred embodiment, the calcium carbonate containing material is natural ground calcium carbonate, the calcium phosphate is dicalcium phosphate, and at least one titanium containing substance is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof and most preferably titanyl sulfate.

[0253] According to another preferred embodiment, the material comprising calcium carbonate is natural ground calcium carbonate, the calcium phosphate is dicalcium phosphate, and the at least one substance comprising titanium is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof, and the at least one titanium-containing substance is added during and / or after step d) and before step e).

[0254] Preferably, the calcium carbonate containing material is provided in the form of an aqueous suspension having a solids content in the range of 1-90 wt.-%, preferably 3-60 wt.-%, more preferably 5-40 wt.-% and most preferably 10-25 wt.-%, based on the total weight of the aqueous suspension, and / or the calcium carbonate containing material is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-40 μm. 50(by weight), and / or a weight top cut particle size d of 0.15-1500 μm, preferably 1-600 μm, more preferably 1.5-300 μm and most preferably 2-80 μm 98 (weight).

[0255] Preferably, the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) or the phosphate ion source selected from phosphoric acid, its salts or mixtures thereof of step B) is provided in the form of an aqueous suspension having a solid content in the range of 1-90 wt. %, preferably 3-60 wt. %, more preferably 5-40 wt. % and most preferably 10-25 wt. %, based on the total weight of the aqueous suspension, and / or the calcium phosphate of step b) is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-40 μm. 50 (weight).

[0256] Additionally or alternatively, the material comprising calcium carbonate is treated with a solution comprising at least one substance comprising titanium in an amount of 0.01-10 wt.-% titanium element, preferably in an amount of 0.1-8 wt.-%, more preferably in an amount of 0.4-5 wt.-% and most preferably in an amount of 0.8-2 wt.-%, based on the total weight of the aqueous solution.

[0257] In another embodiment of the preparation of surface-reacted natural or precipitated calcium carbonate, the inventive method is carried out in the presence of at least one compound selected from silicates, aluminum hydroxide, alkaline earth metal aluminates such as sodium aluminate or potassium aluminate, magnesium oxide, or mixtures thereof. Preferably, at least one silicate is selected from aluminum silicates, calcium silicates, or alkaline earth metal silicates. These components may be added to the aqueous suspension comprising natural or precipitated calcium carbonate before the addition of the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) or the phosphate ion source selected from phosphoric acid, its salts or mixtures thereof of step B).

[0258] Alternatively, the silicate and / or aluminium hydroxide and / or alkaline earth aluminate and / or one (or more) magnesium oxide component may be added to the aqueous suspension of natural or precipitated calcium carbonate when the reaction of the natural or precipitated calcium carbonate with the calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate of step b) or the phosphate ion source selected from phosphoric acid, its salts or mixtures thereof of step B) has already begun. Further details on the preparation of surface-reacted natural or precipitated calcium carbonate in the presence of at least one silicate and / or aluminium hydroxide and / or one (or more) alkaline earth aluminate component are disclosed in WO 2004 / 083316 A1, the content of which is hereby included in the present application.

[0259] The process according to the invention can be carried out as a batch process, a semi-continuous process or a continuous process. If appropriate, process steps d) and / or e) can be repeated once or several times.

[0260] In a batch process, a container may be provided in which the calcium carbonate-containing material of step a) and the calcium phosphate of step b) are mixed with water to form an aqueous suspension according to process step d). Subsequently, the aqueous suspension obtained in step d) is transferred to a grinding device, wherein the aqueous suspension is ground at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species. The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0261] According to an exemplary intermittent process, a first container including a mixing device, a second container including a mixing device and a third container are provided. In a first step, the material and water comprising calcium carbonate of step a) are mixed in the first container. Subsequently, the mixture obtained is transferred to a second container, wherein the calcium phosphate of step b) is added. The aqueous suspension obtained is stored in a third container, whereby the suspension is transferred to a grinding device, wherein the aqueous suspension is ground at a pH value of at least 4.2 to form an aqueous suspension of calcium salt particles through surface reaction. The third container may preferably be equipped with a low-speed mixer so as to mix the aqueous suspension for a long time, for example, for several days. At least one material comprising titanium may be added to the first and / or second and / or third container before and or during the grinding step.

[0262] In a continuous process, a container and a grinding device may be provided. The material comprising calcium carbonate of step a), the calcium phosphate of step b) and water may be fed to the container individually or together, wherein the material comprising calcium carbonate of step a), the calcium phosphate of step b) and water are mixed and the formed aqueous suspension is continuously transferred to the grinding device. The aqueous suspension is ground in the grinding device at a pH of at least 4.2 to form an aqueous suspension of surface-reacted calcium salt particles, which is continuously discharged from the grinding unit. At least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0263] White UV-absorbing surface-reacted calcium carbonate doped with titanium species can be produced by the method of the present invention. The white UV-absorbing surface-reacted calcium carbonate particles doped with titanium species obtained by the method of the present invention may have a volume-determined median particle size d of 0.5-75 μm, preferably 1-50 μm, more preferably 2-40 μm, even more preferably 2.5-30 μm and most preferably 3-15 μm. 50Additionally or alternatively, the surface-reacted calcium salt particles obtained by the process of the present invention may have a volume-determined top cut particle size d of 1-150 μm, preferably 2-100 μm, more preferably 4-80 μm, even more preferably 5-60 μm and most preferably 6-30 μm. 98 (volume).

[0264] The inventors surprisingly found that the co-grinding of a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate with a material comprising calcium carbonate at a pH of at least 4.2 before and / or during and / or after step d) and / or before and / or during step e) and the addition of at least one substance comprising titanium leads to the formation of surface-reacted calcium salt particles doped with titanium substances having a small particle size and a high specific surface area. Without being bound by any theory, the inventors believe that the grinding step of the inventive method provides the benefit of increasing the (chemical) reaction rate of the inventive method by continuously producing freshly prepared and thus reactive surfaces of the raw materials. In addition, the inventors found that the inventive method can utilize crude raw materials and raw materials with lower quality, for example because they contain some impurities. This provides the possibility to utilize materials such as by-products or waste materials of other methods, which are difficult to use in conventional methods for the production of surface-reacted calcium salt particles.

[0265] In addition, the inventors of the present invention have found that the energy generated by the grinding step can be sufficient to cause the conversion into surface-reacted calcium salt particles. This provides the possibility to operate the method at low temperatures and / or using raw materials with room temperature, i.e., 20°C ± 2°C, and thus reduce production costs. Another advantage of the inventive method is that it can be carried out using standard grinding equipment and can be carried out as a continuous method, which helps to produce surface-reacted calcium salt particles. In addition, the inventive method does not require the addition of external carbon dioxide.

[0266] In addition, the inventors surprisingly found that the surface-reacted calcium carbonate particles doped with titanium substances can be prepared by the method of the present invention. The method for producing these particles is an easy and fast method, and the product obtained is affordable and especially easy to handle. The method can be carried out in standard equipment without causing significant burdens to humans and the environment. Such methods and products are advantageous because the final consumer does not have to handle particles containing titanium dioxide in powder form, and the powder contains submicron or nanometer-sized titanium dioxide particles. Therefore, floating dust can be reduced or eliminated, which can occur when two compounds (surface-reacted calcium carbonate and titanium dioxide) are mixed in the form of dry products, which can cause health problems, especially when inhaled. In addition, particle separation during transportation can be reduced or eliminated, which occurs when two compounds (surface-reacted calcium carbonate and titanium-containing materials (e.g., titanium dioxide)) are mixed in the form of dry products.

[0267] According to another preferred embodiment, the calcium carbonate containing material is natural ground calcium carbonate, the phosphate ion source is selected from the phosphoric acid, its salts or mixtures thereof of step B) and is provided in the form of an aqueous suspension having a solids content in the range of 1-90 wt.-%, preferably 3-60 wt.-%, more preferably 5-40 wt.-% and most preferably 10-25 wt.-%, based on the total weight of the aqueous suspension, and at least one titanium containing substance is selected from titanium salts, titanium hydroxide, titanium oxide and mixtures thereof, preferably the titanium containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof and most preferably the titanium containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof and most preferably the titanium containing substance is titanyl sulfate and is added during and / or after step d) and before step e). Preferably, the material comprising calcium carbonate is treated with a solution comprising at least one substance comprising titanium in an amount of 0.01-10 wt.-% of the element titanium, preferably in an amount of 0.1-8 wt.-%, more preferably in an amount of 0.4-5 wt.-% and most preferably in an amount of 0.8-2 wt.-%, based on the total weight of the aqueous solution.

[0268] Additional method steps

[0269] According to one embodiment, the method of the invention further comprises the step of agitating the aqueous suspension after step e). Preferably, the suspension is agitated for at least 1 minute, preferably for at least 5 minutes, more preferably for at least 10 minutes and most preferably for at least 15 minutes.

[0270] According to another embodiment, the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate can be kept in suspension and can be optionally further stabilized by a dispersant. Conventional dispersants known to the skilled person can be used. Preferred dispersants contain polyacrylic acid and / or carboxymethyl cellulose. However, other dispersants are also possible. The skilled person will choose the dispersant according to his equipment and the intended use of the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate. According to a preferred embodiment, the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate is separated from the aqueous suspension, for example by filtration, and thereafter a dispersant is added to the filter cake, preferably in the form of a solution or dispersion. The skilled person knows how to filter and redisperse the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate and will choose the dispersant and separation method according to his equipment and intended use.

[0271] According to further optional embodiments, the solid content of the aqueous suspension obtained by the method according to the invention can be adjusted. For example, water can be added to the suspension until the desired solid content is obtained. Additionally or alternatively, a suspension of solid particles with an appropriately low content can be added to the aqueous suspension of the white UV-absorbing surface-reacted calcium carbonate doped with titanium species until the desired solid content is obtained. Alternatively, the suspension can be partially dehydrated by a filtration method such as nanofiltration or a thermal separation method such as an evaporation method.

[0272] According to an optional embodiment, the method according to the present invention further comprises the step of adjusting the solid content of the aqueous suspension of the white, UV-absorbing, surface-reacted calcium carbonate particles doped with a titanium species formed in step e). According to one embodiment of the present invention, the solid content of the aqueous suspension of the white, UV-absorbing, surface-reacted calcium carbonate particles doped with a titanium species formed in step e) is adjusted so that it is 20-60% by weight, preferably 25-50% by weight, and more preferably 30-45% by weight, based on the total weight of the suspension.

[0273] The aqueous suspension obtained after step e) can be further processed, for example the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species can be separated from the aqueous suspension and / or subjected to a drying step.

[0274] According to one embodiment, the method of the present invention further comprises a step f) of separating the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e). Thus, the method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species may comprise the following steps:

[0275] a) providing a material comprising calcium carbonate,

[0276] b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate,

[0277] c) providing at least one substance comprising titanium, and

[0278] d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and

[0279] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0280] wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO43- ),and

[0281] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e), and

[0282] f) separating the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained from step e).

[0283] Alternatively, a method for making a white UV absorbing surface-reacted calcium carbonate doped with titanium species may include the following steps:

[0284] a) providing a material comprising calcium carbonate,

[0285] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof,

[0286] c) providing at least one substance comprising titanium,

[0287] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0288] e) grinding the aqueous suspension of step D) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0289] wherein the calcium carbonate-containing material of step a) and the phosphate ion source of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0290] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e), and

[0291] f) separating the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained from step e).

[0292] The white UV-absorbing, titanium-doped, surface-reacted calcium carbonate obtained by step e) can be separated from the aqueous suspension by any conventional separation means known to the skilled person. According to one embodiment of the present invention, the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate is mechanically and / or thermally separated in method step f). Examples of mechanical separation methods are filtration (e.g., by drum filters or filter presses), nanofiltration or centrifugation. Examples of thermal separation methods are concentration methods by applying heat, for example, in an evaporator. According to a preferred embodiment, the surface-reacted calcium carbonate is separated in method step f) by solvent evaporation and / or filter press.

[0293] After separation, the white UV-absorbing titanium-doped surface-reacted calcium carbonate may be dried in order to obtain dry white UV-absorbing titanium-doped surface-reacted calcium carbonate. According to one embodiment, the method of the present invention further comprises a step g): drying the white UV-absorbing titanium-doped surface-reacted calcium carbonate after step e) or after step f) (if present) at a temperature in the range of 60-600° C., preferably 80-450° C., most preferably 95-400° C., preferably until the moisture content of the white UV-absorbing titanium-doped surface-reacted calcium carbonate is less than 1% by weight, based on the total weight of the dry white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0294] According to one embodiment, the method of the present invention further comprises a step g) of drying the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e) and / or step f). Thus, the method for producing a white UV absorbing surface-reacted calcium carbonate doped with titanium species may comprise the following steps:

[0295] a) providing a material comprising calcium carbonate,

[0296] b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate,

[0297] c) providing at least one substance comprising titanium, and

[0298] d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and

[0299] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0300] wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1.2+ :PO4 3- ),and

[0301] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e),

[0302] f) separating the white UV-absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e) and

[0303] g) Drying of white UV absorbing surface reacted calcium carbonate doped with titanium species.

[0304] Alternatively, a method for making a white UV absorbing surface-reacted calcium carbonate doped with titanium species may include the following steps:

[0305] a) providing a material comprising calcium carbonate,

[0306] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof,

[0307] c) providing at least one substance comprising titanium,

[0308] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0309] e) grinding the aqueous suspension of step D) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0310] wherein the calcium carbonate-containing material of step a) and the phosphate ion source of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0311] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e), and

[0312] f) separating the white UV-absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e) and

[0313] g) Drying of white UV absorbing surface reacted calcium carbonate doped with titanium species.

[0314] Typically, the drying step g) can occur using any suitable drying equipment and can, for example, include thermal drying and / or drying under reduced pressure using equipment such as evaporators, flash dryers, ovens, spray dryers and / or drying in a vacuum chamber. The drying step g) can be carried out under reduced pressure, ambient pressure or under increased pressure. For temperatures below 100° C., it may be preferred to carry out the drying step under reduced pressure. The drying step can be carried out, for example, for at least 30 seconds, at least 1 minute, 2 minutes, 5 minutes, 10 minutes, 30 minutes, 1 hour, 2 hours, 12 hours or 1 day. The technician can select the drying time according to the equipment, water content and intended use.

[0315] According to a preferred embodiment, the separation is carried out by thermal methods. This allows the white UV-absorbing surface-reacted calcium carbonate doped with titanium species to be subsequently dried without changing the equipment.

[0316] According to one embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species is dried in process step g) until the moisture content of the white UV-absorbing surface-reacted calcium carbonate doped with titanium species is less than or equal to 1.0 wt.-%, preferably less than or equal to 0.5 wt.-% and more preferably less than or equal to 0.2 wt.-%, based on the total weight of the dried white UV-absorbing surface-reacted calcium carbonate doped with titanium species.

[0317] According to another embodiment, the method of the present invention further comprises a step h) of treating the surface of the white UV absorbing surface-reacted calcium carbonate doped with titanium species of the aqueous suspension obtained from step e) and / or step f) and / or step g). Thus, the method for producing a white UV absorbing surface-reacted calcium carbonate doped with titanium species may comprise the following steps:

[0318] a) providing a material comprising calcium carbonate,

[0319] b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate,

[0320] c) providing at least one substance comprising titanium, and

[0321] d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and

[0322] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0323] wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1.2+ :PO4 3- ),and

[0324] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e),

[0325] f) separating the white UV-absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e) and

[0326] g) dry white UV absorbing surface reacted calcium carbonate doped with titanium species, and

[0327] h) treating the surface of the obtained white UV-absorbing surface-reacted calcium carbonate doped with titanium species.

[0328] Alternatively, a method for making a white UV absorbing surface-reacted calcium carbonate doped with titanium species may include the following steps:

[0329] a) providing a material comprising calcium carbonate,

[0330] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof,

[0331] c) providing at least one substance comprising titanium,

[0332] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0333] e) grinding the aqueous suspension of step D) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0334] wherein the calcium carbonate-containing material of step a) and the phosphate ion source of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0335] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e), and

[0336] f) separating the white UV-absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e)

[0337] g) dry white UV absorbing surface reacted calcium carbonate doped with titanium species, and

[0338] h) treating the surface of the obtained white UV-absorbing surface-reacted calcium carbonate doped with titanium species.

[0339] Typically, the treatment step h) can occur using any suitable treatment agent, such as a hydrophobic agent, such as a fatty acid. The treatment agent can be, for example, an aliphatic carboxylic acid having a total carbon atom amount of C4-C24 and / or at least one monosubstituted succinic anhydride consisting of a succinic anhydride monosubstituted with a linear, branched, aliphatic and cyclic group selected from having a total carbon atom amount of C2-C30 in the substituent and / or a phosphate blend of one or more monophosphates and one or more phosphate diesters. Preferred hydrophobic agents are stearic acid and palmitic acid. Such treatment agents are known to the skilled person and are commercially available. The surface treatment of the surface-reacted calcium carbonate doped with a white UV-absorbing titanium substance can affect the rheological properties of the material.

[0340] According to a preferred embodiment of the present invention, there is provided a method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species, comprising the following steps:

[0341] a) providing a material comprising calcium carbonate,

[0342] b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate,

[0343] c) providing at least one substance comprising titanium, and

[0344] d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and

[0345] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0346] wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0347] wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e),

[0348] The dicalcium phosphate is produced by

[0349] i) providing natural ground calcium carbonate,

[0350] ii) Provide phosphoric acid and

[0351] iii) contacting the natural ground calcium carbonate of step i) and the phosphoric acid of step ii) in the presence of water to form dicalcium phosphate,

[0352] The natural ground calcium carbonate of step i) and the phosphoric acid of step ii) are provided in combination in a molar ratio of calcium ions to phosphate ions of 1:2 to 5:1.

[0353] According to another preferred embodiment of the present invention, there is provided a method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species, comprising the following steps:

[0354] a) providing a material comprising calcium carbonate,

[0355] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof,

[0356] c) providing at least one substance comprising titanium, and

[0357] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0358] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0359] wherein the molar ratio of calcium ions to phosphate ions (Ca) is in the range of 1.75:1 to 100:1. 2+ :PO4 3- ) providing the calcium carbonate-containing material of step a) and the phosphate ion source of step b), and

[0360] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0361] According to another preferred embodiment of the present invention, there is provided a method for producing white UV absorbing surface-reacted calcium carbonate doped with titanium species, comprising the following steps:

[0362] a) providing a material comprising calcium carbonate,

[0363] B) provide phosphoric acid,

[0364] c) providing at least one substance comprising titanium, and

[0365] D) treating the calcium carbonate-containing material of step a) with the phosphoric acid of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0366] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0367] wherein the molar ratio of calcium ions to phosphate ions (Ca) is in the range of 1.75:1 to 100:1. 2+ :PO4 3- ) combining to provide the calcium carbonate-containing material of step a) and the phosphoric acid of step b), and

[0368] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0369] White UV absorbing titanium doped surface reacted calcium carbonate

[0370] According to a further aspect of the present invention, a white UV absorbing surface-reacted calcium carbonate doped with a titanium species is provided. A white UV absorbing surface-reacted calcium carbonate doped with a titanium species is obtainable by the inventive method.

[0371] More precisely, a white UV absorbing surface-reacted calcium carbonate doped with titanium species can be obtained by a method comprising the following steps:

[0372] a) providing a material comprising calcium carbonate,

[0373] b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate,

[0374] c) providing at least one substance comprising titanium, and

[0375] d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and

[0376] e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0377] wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0378] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0379] According to another embodiment of the present invention, a white UV absorbing surface-reacted calcium carbonate doped with titanium species can be obtained by a method comprising the following steps:

[0380] a) providing a material comprising calcium carbonate,

[0381] B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof,

[0382] c) providing at least one substance comprising titanium,

[0383] D) treating the calcium carbonate-containing material of step a) with the phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, and

[0384] e) grinding the aqueous suspension of step D) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species,

[0385] wherein the calcium carbonate-containing material of step a) and the phosphate ion source of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:1. 2+ :PO4 3- ),and

[0386] The at least one titanium-containing substance of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

[0387] The white UV absorbing surface-reacted calcium carbonate doped with titanium species obtained by the present invention may be present in a suspension or slurry or may be present as a dry white UV absorbing surface-reacted calcium carbonate doped with titanium species.

[0388] According to one embodiment of the present invention, the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate obtained by the inventive method contains, in addition to calcium carbonate, at least one water-insoluble calcium salt other than calcium carbonate, namely hydroxyapatite. "Hydroxyapatite" also referred to as hydroxyapatite (HA) in the meaning of the present invention is a naturally occurring mineral form of calcium apatite having the formula Ca5(PO4)3(OH). Hydroxyapatite can be further substituted with carbonate ions and / or halides such as fluoride ions, bromide ions, iodide ions, chloride ions or mixtures thereof to replace the hydroxyl groups.

[0389] In addition to hydroxyapatite, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the inventive method may also contain other water-insoluble calcium salts other than calcium carbonate, such as tricalcium phosphate and / or apatite calcium phosphate, preferably octacalcium phosphate, fluoroapatite, carboxyapatite, or mixtures thereof. The surface-reacted calcium salt particles may contain a mass ratio of calcium carbonate to tricalcium phosphate and / or apatite calcium phosphate in the range of 0.05:1 to 59:1, preferably 0.14:1 to 44:1, more preferably 0.2:1 to 29:1, even more preferably 0.3:1 to 15:1 and most preferably 0.5:1 to 5:1.

[0390] According to another embodiment of the present invention, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the inventive method comprises calcite as calcium carbonate. "Calcite" in the meaning of the present invention is the most common crystal polymorph of calcium carbonate and is considered to be the most stable crystalline form of calcium carbonate.

[0391] Besides calcite, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species obtained by the process of the invention may also contain further crystal structures, such as aragonite and / or vaterite.

[0392] According to one embodiment of the present invention, the weight ratio of calcite to hydroxyapatite is from 99:1 to 1:99, based on the dry weight of calcite and the dry weight of hydroxyapatite. According to a preferred embodiment of the present invention, the weight ratio of calcite to hydroxyapatite is from 80:20 to 20:80, more preferably from 70:30 to 30:70 and most preferably from 60:40 to 40:60, based on the dry weight of calcite and the dry weight of hydroxyapatite.

[0393] According to a preferred embodiment of the present invention, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species obtained by the inventive method contains only calcite as calcium carbonate crystal structure, but no further calcium carbonate crystal structures.

[0394] The white, UV-absorbing, surface-reacted calcium carbonate is doped with a titanium substance. "Doping" with a titanium substance in the meaning of the present invention refers to the incorporation or introduction of a titanium substance into the structure of the calcium carbonate. The surface-reacted calcium carbonate doped with a titanium substance may be present only in the outer layer of the surface-reacted calcium carbonate or may be present throughout the surface-reacted calcium carbonate. The doping may be present uniformly or non-uniformly in the surface-reacted calcium carbonate. According to a preferred embodiment of the present invention, the doping with a titanium substance is uniformly present throughout the surface-reacted calcium carbonate. "Doping" in the meaning of the present invention is different from a mere mixture of the surface-reacted calcium carbonate with a titanium substance or a coating with a titanium substance. The technician knows how to measure whether the structure is doped or mixed only with a titanium substance, for example by SEM, EDX or XPS measurement results and UV-visible light measurement results are suitable. For example, by SEM measurement, the technician knows how to distinguish between single particles and attached particles.

[0395] In the meaning of the present invention, titanium material refers to titanium having an oxidation number other than zero. According to one embodiment of the present invention, titanium material in the meaning of the present invention refers to Ti 2+ 、Ti 3+ and / or Ti 4+ , preferably Ti 3+ and / or Ti 4+ And the most preferred Ti 4+ .

[0396] The titanium material is present in an amount of 0.01-20 wt% titanium element, based on the total dry weight of the surface-reacted calcium carbonate. According to a preferred embodiment of the present invention, the titanium material is present in an amount of 0.05-15 wt% titanium element, more preferably 0.1-10 wt% and most preferably 0.5-5 wt%, based on the total dry weight of the surface-reacted calcium carbonate.

[0397] According to one embodiment of the present invention, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the inventive method comprises a 2 / g-200m 2 Particles with a specific surface area of ​​10 m / g, measured using nitrogen and the BET method according to ISO 9277:2010, preferably 10 m 2 / g-180m 2 / g, more preferably 20m 2 / g-170m 2 / g, even more preferably 25m 2 / g-150m 2 / g and most preferably 30m 2 / g-100m 2 / g, which is measured using nitrogen and the BET method according to ISO 9277:2010. The BET specific surface area in the meaning of the present invention is defined as the surface area of ​​the particles divided by the mass of the particles. The specific surface area as used herein is measured by adsorption using the BET isotherm (ISO 9277:2010) and is specified in m 2 The unit is / g.

[0398] According to another embodiment of the present invention, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the inventive method comprises a 2 / g-200m 2 / g, preferably 10m 2 / g-180m 2 / g, more preferably 20m 2 / g-170m 2 / g, even more preferably 25m 2 / g-150m 2 / g and most preferably 30m 2 / g-100m 2 / g of particles with a specific surface area (BET) of 1.340 nm / g, which is measured using nitrogen and the BET method, and the surface-reacted calcium carbonate particles contain a mass ratio of calcium carbonate (preferably calcite) to hydroxyapatite in the range of 99:1 to 1:99, based on the dry weight of calcium carbonate (preferably calcite) and the dry weight of hydroxyapatite, preferably a weight ratio of calcium carbonate (preferably calcite) to hydroxyapatite of 80:20 to 20:80, more preferably 70:30 to 30:70 and most preferably 60:40 to 40:60, based on the dry weight of calcium carbonate (preferably calcite) and the dry weight of hydroxyapatite.

[0399] According to one embodiment, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species obtained by the process of the present invention has a volume-determined median particle size d of 0.5-75 μm, preferably 1-50 μm, more preferably 2-40 μm, even more preferably 2.5-30 μm and most preferably 3-15 μm. 50 (volume).

[0400] Additionally or alternatively, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the process of the present invention has a volume-determined top cut particle size d of 1-150 μm, preferably 2-100 μm, more preferably 4-80 μm, even more preferably 5-60 μm and most preferably 6-30 μm. 98 (volume).

[0401] Value d x represents such a diameter: x% of the particles have a diameter smaller than d x This means that d98 The value is the particle size at which 98% of all particles are smaller. 98 Values ​​are also specified as "top cut". d x Values ​​may be given as volume or weight percent. 50 The (weight) value is therefore the weight median particle size, ie the particle size below which 50% by weight of all grains are smaller, and d 50 The (volume) value is the volume median grain size, ie the grain size below which 50% by volume of all grains are smaller.

[0402] The volume median particle diameter d was estimated using a Malvern Mastersizer 3000 laser diffraction system. 50 d measured using a Malvern Mastersizer 3000 laser diffraction system 50 or 98 The value indicates the diameter value such that 50% or 98% of the particles by volume, respectively, have a diameter smaller than this value. The raw data obtained by the measurement were analyzed using Mie theory, with the particle refractive index being 1.57 and the absorptivity being 0.005.

[0403] Methods and instruments are known to the skilled person and are commonly used for determining the crystallite size of fillers and pigments.

[0404] The white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the method of the present invention may have a range of 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particles in the range of / g was calculated from the mercury porosimetry measurements.

[0405] The particle internal pore size of the white UV-absorbing surface-reacted calcium carbonate doped with titanium species is preferably in the range of 0.004-1.6 μm, more preferably in the range of 0.005 to 1.3 μm, particularly preferably 0.006-1.15 μm and most preferably 0.007 to 1.0 μm, for example 0.1 to 0.6 μm, as determined by mercury porosimetry measurements.

[0406] The specific pore volume was measured using mercury intrusion porosimetry using a Micromeritics Autopore V 9620 mercury intrusion porosimeter with a maximum applied pressure of 414 MPa (60,000 psi) of mercury equivalent to a Laplace throat of 0.004 μm (~nm). The equilibrium time used at each pressure step was 20 seconds. The sample material was sealed in a 5 cm3 The data were corrected for mercury compression, penetrometer expansion, and sample material compression using the software Pore-Comp (Gane, PAC, Kettle, JP, Matthews, GP, and Ridgway, CJ, "Void Space Structure of Compressible Polymer Spheres and Consolidated Calcium Carbonate Paper-Coating Formulations", Industrial and Engineering Chemistry Research, 35(5), 1996, pp. 1753-1764).

[0407] The total pore volume seen in the cumulative intrusion data can be divided into two regions where the intrusion data drops from 214 μm to about 1-4 μm, showing coarse packing of the sample between any strongly contributing aggregate structures. Below these diameters is the inter-particle packing of the particles themselves. If they also have intra-particle pores, this region appears bimodal, and the intra-particle specific pore volume is defined by taking the specific pore volume of the mercury intrusion into pores finer than the modal inflection point (i.e. finer than the bimodal inflection point). The sum of these three regions yields the overall pore volume of the powder, but is strongly dependent on the original sample compaction / sedimentation of the powder at the coarse pore end of the distribution.

[0408] By taking the first derivative of the cumulative intrusion curve, the pore size distribution based on the equivalent Laplace diameter is revealed, which inevitably includes pore shielding. The differential curve clearly shows the coarse aggregate pore structure region, the inter-particle pore region, and the intra-particle pore region (if any). Knowing the intra-particle pore size range, the remaining inter-particle and inter-aggregate pore volume can be subtracted from the total pore volume to provide the required pore volume of the individual internal pores based on the pore volume per unit mass (specific pore volume). Of course, the same subtraction principle applies to isolating any other pore size region of interest.

[0409] According to one embodiment of the present invention, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the method of the present invention has

[0410] (i)5m 2 / g-200m 2 / g, preferably 10m 2 / g-180m 2 / g, more preferably 20m 2 / g-170m 2 / g, even more preferably 25m 2 / g-150m2 / g and most preferably 30m 2 / g-100m 2 Specific surface area of ​​100 g / m, measured using nitrogen and the BET method according to ISO 9277:2010, and / or

[0411] (ii) a volume-determined median particle size d of 0.5-75 μm, preferably 1-50 μm, more preferably 2-40 μm, even more preferably 2.5-30 μm and most preferably 3-15 μm 50 (volume), and / or

[0412] (iii) a volume-determined top cut particle size d of 1-150 μm, preferably 2-100 μm, more preferably 4-80 μm, even more preferably 5-60 μm and most preferably 6-30 μm 98 (volume), and / or

[0413] (iv) 0.1-2.3 cm 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.8cm 3 / g and most preferably 0.6-1.6cm 3 The intrusion specific pore volume in the particles is in the range of 100 Å / g, which is calculated from the mercury porosimetry measurements.

[0414] According to one embodiment of the present invention, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the method of the present invention has

[0415] (i)5m 2 / g-200m 2 / g, preferably 10m 2 / g-180m 2 / g, more preferably 20m 2 / g-170m 2 / g, even more preferably 25m 2 / g-150m 2 / g and most preferably 30m 2 / g-100m 2 Specific surface area of ​​100 g / m, measured using nitrogen and the BET method according to ISO 9277:2010, and / or

[0416] (ii) Volume-determined median particle size d of 2.5-30 μm 50 (volume).

[0417] According to one embodiment, the white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the process of the present invention has a volume-determined median particle size d of 2.5-30 μm. 50 (volume) and a weight ratio of calcite to hydroxyapatite of 70:30 to 30:70, based on the dry weight of calcite and the dry weight of hydroxyapatite.

[0418] The white UV-absorbing titanium-doped surface-reacted calcium carbonate obtainable by the process of the present invention can be provided in the form of a suspension of white UV-absorbing titanium-doped surface-reacted calcium carbonate, as a separate white UV-absorbing titanium-doped surface-reacted calcium carbonate or as a dried white UV-absorbing titanium-doped surface-reacted calcium carbonate. According to a preferred embodiment, the white UV-absorbing titanium-doped surface-reacted calcium carbonate obtainable by the process of the present invention is a dried white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0419] If the white UV-absorbing titanium-doped surface-reacted calcium carbonate obtained by the process of the present invention is dried, the moisture content of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate is less than or equal to 1.0 wt. %, preferably less than or equal to 0.5 wt. %, and more preferably less than or equal to 0.2 wt. %, based on the total weight of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate. According to another embodiment, the moisture content of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate is between 0.01 and 0.15 wt. %, preferably between 0.02 and 0.10 wt. % and more preferably between 0.03 and 0.07 wt. %, based on the total weight of the dried white UV-absorbing titanium-doped surface-reacted calcium carbonate.

[0420] The white UV-absorbing, titanium-doped, surface-reacted calcium carbonate of the present invention may also be provided and / or used in the form of a composition. According to one aspect of the present invention, a composition comprising the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate of the present invention is provided. The composition may also contain other filler materials such as natural ground calcium carbonate, precipitated calcium carbonate and mixtures thereof. The composition may contain the white UV-absorbing, titanium-doped, surface-reacted calcium carbonate obtained by the method of the present invention in an amount of at least 20 wt. %, preferably at least 40 wt. %, more preferably at least 60 wt. % and most preferably at least 80 wt. %, based on the total weight of the composition.

[0421] The inventors have surprisingly discovered that the surface-reacted calcium carbonate formed by the process of the present invention provides additional functionality due to doping the surface-reacted calcium carbonate with a titanium-containing species.

[0422] For example, the inventors of the present invention have found that surface-reacted calcium carbonate doped with titanium species absorbs at least some of the UV radiation in the range of 280-400 nm. Thus, the inventive surface-reacted calcium carbonate obtained by the process of the present invention can be used for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

[0423] Furthermore, the inventors of the present invention have discovered that the surface-reacted calcium carbonate doped with titanium species is white and can therefore be used in suspensions, dispersions or slurries of minerals, fillers or pigments, which are typically used in polymer applications, paper coating applications, papermaking, paints, coatings, sealants, adhesives, feeds, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications and provide a white appearance without the addition of additional pigments.

[0424] Furthermore, the inventors surprisingly found that the titanium species cannot be separated from the surface-reacted calcium carbonate by washing alone or in a liquid composition due to doping.

[0425] Furthermore, the inventors surprisingly found that white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species has a high surface area, which is an essential prerequisite for several applications.

[0426] Because the white, UV-absorbing, surface-reacted calcium carbonate is doped with titanium species, titanium dioxide particles in the submicron and / or nanometer size range do not need to be labeled in ingredient lists and should therefore have a higher acceptance by end consumers.

[0427] Use of white UV absorbing titanium doped surface reacted calcium carbonate

[0428] White, UV absorbing, surface-reacted calcium carbonate doped with titanium species can be used in a variety of applications.

[0429] According to one embodiment, the white UV absorbing surface-reacted calcium carbonate doped with titanium species obtained by the process of the present invention or a composition comprising the same is used in polymer applications, paper coating applications, papermaking, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications. The engineered wood application may be included in an engineered wood product such as a wood composite, preferably a medium density fiberboard or a particleboard.

[0430] According to another embodiment of the present invention, the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species obtained by the process of the present invention or a composition comprising the same is used for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

[0431] The inventors surprisingly found that such white, UV-absorbing, surface-reacted calcium carbonate doped with titanium species or compositions comprising the same, obtained by the process of the present invention, provide adequate sun protection for living cells, and in particular human skin.

[0432] According to one embodiment of the invention, the cosmetic preparation is a sun protection product, a facial makeup, a hair care product, a hand care product, a skin care product, a body care product and mixtures thereof.

[0433] The inventive white UV-absorbing surface-reacted calcium carbonate doped with titanium species obtained by the process of the present invention or a composition comprising the same can be incorporated into an article so as to provide an article with enhanced white color and / or enhanced UV-absorbing properties. According to a further aspect of the present invention, an article comprising the surface-reacted calcium carbonate or a composition comprising the same obtainable by the process according to the present invention is provided, wherein the article is selected from paper products, engineered wood products, gypsum board products, polymer products, hygiene products, medical products, health products, filtration products, woven materials, nonwoven materials, geotextile products, agricultural products, horticultural products, clothing, footwear products, luggage products, household products, industrial products, packaging products, building products and construction products.

[0434] The scope and concerns of the present invention will be better understood based on the following examples, which are intended to illustrate some embodiments of the invention and are non-limiting.

[0435] Examples

[0436] 1. Measurement method

[0437] Hereinafter, the measurement method performed in the examples is described.

[0438] 1.1 Particle size distribution

[0439] The volume-determined median particle size d was evaluated using a Malvern Mastersizer 3000 laser diffraction system (Malvern Instruments Plc, UK). 50 (volume) and volume-determined top cut particle size d 98 (volume). d 50 (volume) or d 98The (volume) value indicates the diameter value such that 50% or 98% of the particles by volume, respectively, have a diameter smaller than this value. The raw data obtained by the measurement are analyzed using Mie theory, with a particle refractive index of 1.57 and an absorptivity of 0.005. The method and the instrument are known to the skilled person and are commonly used for determining the particle size distribution of fillers and pigments. The samples are measured under dry conditions without any prior treatment.

[0440] The median particle size d is determined by weight measurement using the sedimentation method. 50 (weight) and weight-determined top cut particle size d 98 (weight), the sedimentation method is the analysis of sedimentation behavior in a gravitational field. The measurement was performed using a Sedigraph from Micromeritics Instrument Corporation, USA TM The method and the apparatus are known to the skilled person and are commonly used for determining the particle size distribution of fillers and pigments. The measurement is carried out in a 0.1 wt. % aqueous solution of Na4P2O7. The sample is dispersed and sonicated using a high-speed stirrer.

[0441] Methods and instruments are known to the skilled person and are commonly used for determining the crystallite size of fillers and pigments.

[0442] 1.2. Specific surface area (SSA)

[0443] The specific surface area is measured via the BET method according to ISO 9277:2010 using nitrogen and an ASAP 2460 instrument (Micromeritics GmbH, Germany), followed by conditioning the sample by heating for a period of 30 minutes at 100° C. Prior to such measurement, the sample is filtered in a Büchner funnel, rinsed with deionized water and dried in an oven at 110° C. for at least 12 hours.

[0444] 1.3 X-ray diffraction (XRD)

[0445] XRD experiments were performed using a rotatable PMMA holder ring on the sample. The samples were analyzed using a Bruker D8 advanced powder diffractometer following the Bragg principle. This diffractometer contains a 2.2kW X-ray tube, sample holder, θ-θ-goniometer and detector. Nickel-filtered Cu-Kα radiation was used in all experiments. The graphs were automatically recorded in 2θ (XRD GV_7600) using a scan rate of 0.7° / min. The obtained powder diffraction patterns were classified by mineral content using the DIFFRACS suite software packages EVA and SEARCH based on reference patterns from the ICDD PDF-2 database (XRDLTM_7603).

[0446] Quantitative analysis of diffraction data refers to the determination of the amounts of different phases in a multiphase sample and has been performed using the DIFFRAC suite software package TOPAS. In detail, quantitative analysis allows the determination of structural properties and phase ratios with quantifiable numerical accuracy from the experimental data itself. This involves modeling the full diffraction pattern using the Rietveld method so that the calculated pattern(s) replicate the experimental pattern.

[0447] 1.4 Reflectivity measurement

[0448] Reflectance analysis was performed using a dual beam PerkinElmer Lambda 950 UV / Visible / NIR spectrophotometer equipped with a 150 mm integrating sphere with a PMT and InGaAs detector.

[0449] The prepared dry composition was measured by reflectance spectroscopy. The dry composition was loaded into a sealed aluminum cup for powder sample placed flush with the reflection port of the integrating sphere for analysis. The spectrophotometer was scanned in the range of 280nm–800nm ​​with a step size of 2nm. The Spectralon white standard was used as a 100% baseline. To obtain a surrogate of the absorbance spectrum of the dry composition, the Kubelka-Munk equation KM=K / S=(1-R) ​​was used. 2 The measured reflectance spectrum is converted to / 2R, where R is the reflectance and K and S are the absorption and scattering coefficients, respectively.

[0450] 1.5 (XRF) Measurement

[0451] 11.5 g of the dried sample was pressed into tablets using a press at 400 kN. TM The elemental composition of the samples was measured using a PERFORM'X X-ray fluorescence spectrometer (Thermo Fisher Scientific, Inc., USA). Quantification was performed using an external calibration specifically prepared for calcium carbonate.

[0452] 1.6. Specific Grinding Energy (SGE)

[0453] The specific grinding energy (SGE) was calculated by first simultaneously recording the power consumption (P) of the grinding apparatus in kW and the volume flow rate (v s )(in m 3 / h) and is indicated in the corresponding monitoring display. In addition, the total solids (TS) content of the feed slurry (in weight %) is determined using a moisture analyzer HR73 from Mettler-Toledo (T = 120 ° C, automatic shut-off 3, standard drying) using a sample size of 5 to 20 g. The density of water (ρ w) is 1.00T / m 3 and the density of the applied dry calcium carbonate / marble / chalk (ρ c ) is 2.71T / m 3 , then SGE can be calculated as a function of given quantities, as expressed in equations (1), (2) and (3).

[0454] SGE=P / ((TS)·m s ) Equation (1)

[0455] m s =ρ s ·v s Equation (2)

[0456] ρ s =[ρ c ·ρ w ] / [ρ c ·(1-(TS))+ρ w ·(TS)] Equation (3)

[0457] 2. Materials and Equipment

[0458] Materials containing calcium carbonate:

[0459] GCCI: Ground marble calcium carbonate from Carrera, Italy. The ground calcium carbonate has a median particle size distribution based on weight. 50 7.9 μm, as determined by sedimentation.

[0460] H3O + Ion donor:

[0461] Phosphoric acid (H3PO4), available from VWR Chemicals (orthophosphoric acid ≥ 85%),

[0462] Substances containing titanium:

[0463] Titanyl sulfate / TiOSO4×H2O, available from Sigma-Aldrich as serial number 14023

[0464] 3. Sample Preparation

[0465] 8 liters of an aqueous slurry of GCCI was prepared in a mixing vessel by adjusting the amount to a solid content of 14 wt %, based on the total weight of the aqueous slurry.

[0466] Separately, a titanyl sulfate solution was prepared by adding 205.2 grams of TiOSO4×H2O salt to 2052.3 g of deionized water. After mixing for about 5 minutes, the solution was then added to 1228.5 g of 30 wt % phosphoric acid and mixed for about 5 to 10 minutes. While mixing the resulting reaction mixture at room temperature, it was added to the above calcium carbonate slurry over a period of 10 minutes. The GCCI and dicalcium phosphate combination obtained from phosphoric acid and GCCI had a calcium ion to phosphate ion molar ratio (Ca 2+) of 3.26:1. 2+ :PO4 3- ).

[0467] The resulting slurry was then removed and aged overnight, after which it was ground for a period of time using a horizontal ball mill (Dynomill Multilab WAB Bachofen) with zirconium-yttrium grinding media (Silibeads ZY-S, 0.4-0.6 mm). The product was passed through the grinding chamber twice to obtain the desired PSD. Sample 1 was then dried at 120° C. and sent for XRD, which confirmed conversion to hydroxyapatite.

[0468]

Claims

1. A method for producing white UV absorbing titanium-doped surface-reacted calcium carbonate comprising the following steps: a) providing a material comprising calcium carbonate, b) providing a calcium phosphate selected from monocalcium phosphate and / or dicalcium phosphate, c) providing at least one substance comprising titanium, and d) treating the calcium carbonate-containing material of step a) with the calcium phosphate of step b) in an aqueous medium to form an aqueous suspension and e) grinding the aqueous suspension of step d) at a pH of at least 4.2 to form a white, UV-absorbing aqueous suspension of surface-reacted calcium carbonate doped with titanium species, wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.75:1 to 100:

1. 2+ :PO4 3- ),and wherein the at least one substance comprising titanium of step c) is added before and / or during and / or after step d) and / or before and / or during step e).

2. The method according to claim 1, wherein the material comprising calcium carbonate is natural ground calcium carbonate and / or precipitated calcium carbonate, preferably the natural ground calcium carbonate is selected from marble, chalk, limestone and mixtures thereof, and / or the precipitated calcium carbonate is selected from precipitated calcium carbonate having aragonite, vaterite or calcite crystal form and mixtures thereof.

3. The method according to claim 1 or 2, wherein the calcium carbonate containing material is in the form of particles having a weight median particle size d of 0.05-500 μm, preferably 0.2-200 μm, more preferably 0.4-100 μm and most preferably 0.6-20 μm. 50 (by weight), and / or a weight top cut particle size d of 0.15-1500 μm, preferably 1-600 μm, more preferably 1.5-300 μm and most preferably 2-80 μm 98 (weight).

4. A method according to any one of the preceding claims, wherein the calcium carbonate-containing material of step a) and the calcium phosphate combination of step b) have a calcium ion to phosphate ion molar ratio (Ca 2+) in the range of 1.9:1 to 75:1, preferably 2:1 to 50:1, more preferably 2.2:1 to 25:1 and most preferably 2.5:1 to 10:

1. 2+ :PO4 3- ).

5. The method according to any one of the preceding claims, wherein the calcium phosphate of step b) is dicalcium phosphate dihydrate and is provided in an amount of 1.7-230 wt. %, based on the total weight of the calcium carbonate-containing material of step a), preferably 2.3-191 wt. %, more preferably 3.5-172 wt. % and most preferably 19-115 wt. %, or wherein the calcium phosphate of step b) is anhydrous dicalcium phosphate and is provided in an amount of 1.4-181 wt %, based on the total weight of the calcium carbonate-containing material of step a), preferably 1.8-151 wt %, more preferably 2.8-136 wt % and most preferably 15-91 wt %, or wherein the calcium phosphate of step b) is anhydrous monocalcium phosphate and is provided in an amount of 1.2-94 wt %, based on the total weight of the calcium carbonate-containing material of step a), preferably 1.6-84 wt %, more preferably 2.4-78 wt % and most preferably 12-59 wt %, or wherein the calcium phosphate of step b) is monocalcium phosphate monohydrate and is provided in an amount of 1.3-100 wt %, based on the total weight of the calcium carbonate-containing material of step a), preferably 1.7-90 wt %, more preferably 2.5-84 wt % and most preferably 13-63 wt %.

6. The method according to any one of the preceding claims, wherein the at least one titanium-containing substance is selected from titanium salts, titanium hydroxide, titanium dioxide and mixtures thereof, preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate, titanium hydroxide, titanium dioxide and mixtures thereof, and most preferably the titanium-containing substance is selected from titanium bromide, titanium fluoride, titanium iodide, titanium chloride, titanyl sulfate and mixtures thereof.

7. The method according to any one of the preceding claims, wherein the at least one substance comprising titanium is provided in an amount of 0.1-20 wt.% of the element titanium, based on the total dry weight of the material comprising calcium carbonate, preferably 0.5-15 wt.%, more preferably 1.0-10 wt.% and most preferably 2.5-7.5 wt.%.

8. The process according to any one of the preceding claims, wherein the aqueous suspension formed in step d) has a solids content of 1-95 wt.-%, preferably 3-75 wt.-%, more preferably 5-50 wt.-%, even more preferably 7-30 wt.-%, even more preferably 9-25 wt.-% and most preferably 10-20 wt.-%, based on the total weight of the aqueous suspension, and / or wherein in step d) the material comprising calcium carbonate is treated with a solution comprising the calcium carbonate of step b) and the at least one substance comprising titanium of step c).

9. The process according to any one of the preceding claims, wherein step e) is carried out at a pH value of 4.5-14, preferably at a pH value of 4.7-13.5, more preferably at a pH value of 5-13, even more preferably at a pH value of 5.5-12.5, even more preferably at a pH value of 6-12 and most preferably at a pH value of 6.0-8.

0.

10. The process according to any one of the preceding claims, wherein step d) and / or step e) is performed at a temperature of 10-100°C, preferably 15-80°C, more preferably 20-50°C and most preferably 20±2°C.

11. The method according to any one of the preceding claims, wherein the dicalcium phosphate is produced by the following steps: i) providing a source of calcium ions other than dicalcium phosphate, preferably providing a material comprising calcium carbonate, more preferably providing natural ground calcium carbonate, ii) providing a phosphate ion source selected from phosphoric acid, its salts and mixtures thereof, preferably phosphoric acid, and iii) contacting the calcium ion source of step i) and the phosphate ion source of step ii) in the presence of water to form dicalcium phosphate, wherein the source of calcium ions of step i) and the source of phosphate ions of step ii) are provided in combination in a molar ratio of calcium ions to phosphate ions of 1:2 to 5:1, preferably 2:3 to 2:1, more preferably 3:4 to 3:2, even more preferably 5:6 to 4:3, still more preferably 10:11 to 11:10 and most preferably about 1:

1.

12. The method according to any one of claims 1 to 10, wherein steps b) and d) are replaced by the following steps B) and D): B) providing a phosphate ion source selected from phosphoric acid, a salt thereof or a mixture thereof, and D) treating said calcium carbonate-containing material of step a) with said phosphate ion source of step B) in an aqueous medium to form an aqueous suspension comprising dicalcium phosphate, wherein the molar ratio of calcium ions to phosphate ions (Ca) is in the range of 1.75:1 to 100:

1. 2+ :PO4 3- ) provide the calcium carbonate-containing material of step a) and the phosphate ion source of step b).

13. The method according to any one of claims 11 or 12, wherein the phosphate ion source is phosphoric acid, a non-hydrogen-containing salt of phosphoric acid, a monohydrogen salt of phosphate, preferably Na2HPO4, or a dihydrogen salt of phosphate, or a mixture thereof, preferably the phosphate ion source is phosphoric acid, a dihydrogen salt of phosphate, or a mixture thereof, preferably the phosphate ion source is selected from phosphoric acid, NaH2PO4, KH2PO4, LiH2PO4, NH4H2PO4, Ca(H2PO4)2, Mg(H2PO4)2, and a mixture thereof.

14. The method according to any one of the preceding claims, wherein the method further comprises a step f) of separating the white UV absorbing surface-reacted calcium carbonate doped with titanium species from the aqueous suspension obtained in step e), and preferably step f) is performed by solvent evaporation and / or filter pressing, and / or The method further comprises a step g): drying the surface-reacted calcium carbonate doped with titanium species at a temperature in the range of 60-600° C., preferably 80-450° C., most preferably 95-400° C., after step e) or after step f) if present, preferably until the moisture content of the surface-reacted calcium carbonate doped with titanium species is less than 1 wt.-%, based on the total weight of the dried surface-reacted calcium carbonate.

15. White, UV-absorbing, surface-reacted calcium carbonate doped with titanium species obtainable by any one of claims 1 to 14.

16. Use of the white UV absorbing titanium doped surface reacted calcium carbonate according to claim 15 in polymer applications, paper coating applications, papermaking, paints, coatings, sealants, adhesives, feed, pharmaceuticals, concrete, cement, cosmetics, water treatment, engineered wood applications, gypsum board applications, packaging applications, catalysis, gas treatment applications and / or agricultural applications.

17. Use of the white, UV-absorbing, surface-reacted calcium carbonate doped with titanium substances according to claim 15 for sun protection of plants and parts thereof or for chemical and physical sun protection in cosmetic preparations.

18. An article comprising the white, UV absorbing, surface-reacted calcium carbonate doped with titanium species according to claim 15, wherein the article is selected from the group consisting of paper products, engineered wood products, gypsum board products, polymer products, hygiene products, medical products, health products, filtration products, woven materials, nonwoven materials, geotextile products, agricultural products, horticultural products, clothing, footwear products, luggage products, household products, industrial products, packaging products, building products and construction products.